A novel method for generating optimal DTM in tropical peatlands using GEDI and ICESat-2 observations - Yuan Sun; Huan Xie; Xiaohua Tong; Yi Li; Alexander R. Cobb; Rahayu S. Sukri; Muhammad Arif bin Haji Selamat; Hao Tang (Remote Sensing of Environment, 2026)

Suppression of microRNAs targeting key MEP pathway genes affects plastid terpenoid content and photosynthesis under variable light conditions - Syed Muhammad Iqbal Syed Othman; Arif Faisal Mustaffa; Muhammad Sajad; Muhamad Hafiz Che-Othman; Hoe-Han Goh; Ismanizan Ismail (Molecular Biology Reports, 2026)

Suppression of miR426 enhances photoprotection and chlorophyll stability via upregulation of ELIP2 in Arabidopsis thaliana - Arif Faisal Mustaffa; Syed Muhammad Iqbal Syed Othman; Nur Irdina Izzatie Mohd Zahid; M. Hafiz Che-Othman; Hoe-Han Goh; Muhammad Sajad; Ismanizan Ismail (Molecular Biology Reports, 2026)

Numerical investigation of PCM-based thermal energy storage device of nuclear power plants containment using a fins configuration - Muhammad Adnan; Hui Wang; Yanlu Wang; Cao Xiaxin; Hailemichael Guadie Mengsitu; Arif Aziz; Jamil Khan (Annals of Nuclear Energy, 2026)

Metabolic repatterning of volatile organic compounds during viral infection in passion fruit - Atul Kumar Srivastava; Junmei Jiang; Jinxi Zhang; Muhammad Arif; Ali Kamran; Nuo Zhang; Akhil Kumar; Xiangyang Li; Xin Xie (Physiological and Molecular Plant Pathology, 2026)

A review of natural hydrogen generation from iron-rich rocks: Mechanisms, influencing factors, techniques, and knowledge gaps - Kaveh Moghanirahimi; Lionel Esteban; Marina Pervukhina; Muhammad Arif; Stefan Iglauer; Alireza Keshavarz (Earth-Science Reviews, 2026)

PCR-based detection of Chicken Anemia Virus and Escherichia coli co-infection in commercial poultry flocks in Lahore, Punjab, Pakistan - Nimra Arif; Shahan Azeem; Aftab Ahmad Anjum; Muhammad Hassan Mushtaq (Veterinary Research Communications, 2026)

Unravelling the functioning of andesitic volcanic aquifers in the equatorial zone using isotopic, age-dating and geochemical tracers - Antoine Picard; Florent Barbecot; Lucas Jurain; Patrick Lachassagne; Nicolas Patris; Jürgen Sültenfuß; Arif Fadillah; Azwar Satrya Muhammad; Nathalie Dörfliger; Heru Hendrayana (Applied Geochemistry, 2026)

Performance analysis of a helium-nitrogen binary gas mixture centrifugal compressor for terrestrial gas-cooled reactor power plants of closed Brayton cycles - Arif Aziz; Qun Zheng; Adil Malik; Muhammad Haris; Ghulam Ishaque; Shadman Ahmad Khattak (Annals of Nuclear Energy, 2026)

Fertilizing Effect of Codium flabellatum and Aspergillus japonicus (Algal-Fungal) Nexus Improves Growth, Nutrient Fluxes and Fruit Quality in Brassica napus in Saline Condition - Ayesha; Humaira Gul; Mamoona Rauf; Asma Tabassum; Aliya Rehman; Muhammad Arif; Muhammad Hamayun; Mohamed A. El-Sheikh; Zainul Abideen (Journal of Soil Science and Plant Nutrition, 2026)

Molecular target for neuroinflammation and pain management: transient receptor potential vanilloid 1 - Zunera Chauhdary; Muhammad Saad Masood; Muhammad Irfan; Amina Shafi; Duryab Rafique; Abeesha Arif; Maryam Akmal (Inflammopharmacology, 2026)

Microbe-mediated drought stress alleviation: Fusarium verticillioides enhances maize growth by upregulation of physiological, biochemical, and molecular responses - Raid Ali; Humaira Gul; Mamoona Rauf; Sajid Ali; Muhammad Arif; Sumera Afzal Khan; Anwar Hussain; Bokyung Lee; Muhammad Hamayun (South African Journal of Botany, 2026)

BrAKT1 overexpression enhances clubroot susceptibility through dysregulation of host physiological processes in pak choi - Samiah Arif; Yǔmeng Yan; Yufan Ge; Muhammad Sanaullah Malik; Ping Li; Saeed ur Rahman; Yidong Zhang (Physiological and Molecular Plant Pathology, 2026)

Pollutant triggers at ocean interfaces: how microhabitats rewire microbial biodegradation and valorization - Mati Ullah; Muhammad Arif; Wajid Hussain; Tariq Ahmad (Marine Chemistry, 2026)

Reconstruction of the circa 8th–9th century CE eruption of Mt. Sindoro that destroyed the Matarām Kingdom–era site of Liyangan, Central Java, Indonesia - Indranova Suhendro; Clive Oppenheimer; Haryo Edi Wibowo; T. Fariz Mohammad; Rara Audery Dini Lesmana; Karenina Intan Indrayani; Wijdan Annafi’ Ahmad; Andhika Nugraha; Muhammad Alsamtu Tita Sabila Pratama Suhartono; Danang Sri Hadmoko; Arif Ashari (Journal of Volcanology and Geothermal Research, 2026)

Retraction Note: Bio-Graphene Foam: A Robust Solution for Adsorptive and Sustainable Chlorophenol Removal from Wastewater - Sidra; Muhammad Hamid khan; Wang Jin Quan; Shakeel Ahmad; Jingling Ji; Xinhua Xiao; Haseen Ullah; Arif Nawaz; Farman Ali; Nisar Ali (Water, Air, & Soil Pollution, 2026)

A Fibrous Thin Film Based on Silver(I) Metal–Organic Framework/Polyethersulfone Composite with Excellent Antibacterial Properties and Photocatalytic Degradation of Methylene Blue - Humaira Shaheen; Abdul Rauf; Muhammad Arif; Muhammad Akram; Komal Aroosh; Mehdi Hassan; Muhammad Jahangir (Water, Air, & Soil Pollution, 2026)

Hydro-economic modelling and climate change in the Murray-Darling Basin, Australia: Applications and implications - Muhammad Arif Watto; Shokhrukh Jalilov; Shahriar Wahid; David Robertson (Water Security, 2026)

Molecular characterization and in silico analysis of the malate dehydrogenase (MDH) gene family in wheat (Triticum aestivum L.) with expression profiling under heavy metal stresses - Mingfang Yang; Amna Abdul Rahim; Haris Khurshid; Laraib Malik; Mohamed A. El-Sheikh; Hafiz Mamoon Rehman; Yingping Tian; Muhammad Arif (Journal of Hazardous Materials, 2026)

The rise of MXene: A new paradigm in 2D materials for energy storage devices - Muhammad Kaleem Shabbir; Javeed Akhtar; Fozia Arif; Haleema Asghar; Imamdin Chandio; Hafsa Khurshid; Khalid Hussain Thebo; Mohamed H. Helal (Journal of Environmental Chemical Engineering, 2026)

Cytotoxic and computational profiling of 2-mercaptobenzimidazole Mannich derivatives: structure activity relationship and carbonic anhydrase binding assessment - Muhammad Naeem; Arooj Mohsin Alvi; Muhammad Mehmmod Moin Ul Haq; Najia Shabbir; Shumaila Mehdi; Areen Khalid; Saqib Khan; Hafiz Muhammad Ahmad; Najm Ul Hassan Khan; Muhammad Nouman Arif; Hafiz Aamir Ali Kharl (Inflammopharmacology, 2026)

Multi-trait plant growth-promoting endophytic fusarium proliferatum from phoenix dactylifera enhanced wheat growth under drought stress condition - Salman Khan; Khalil Ur Rahman; Nida Karishma; Mamoona Rauf; Humaira Gul; Muhammad Hamayun; Abdulwahed Fahad Alrefaei; Faheem Anwar; Sajid Ali; Muhammad Arif (Acta Physiologiae Plantarum, 2026)

Population genomic assessment of the endangered endemic catfish Glyptothorax stocki reveals distinct lineages in Pakistan - Mohsan Raza; Arif Muhammad Khan; Chenhong Li (Hydrobiologia, 2026)

Comparative in vitro pathogenicity of different oil-based formulations of Metarhizium anisopliae against three different aphid species - Ahmad Nawaz; Anam Ejaz; Tariq Mustafa; Usman Naeem; Amna Irshad; Muhammad Dildar Gogi; Muhammad Tayyib; Muhammad Naveed; Amjad Abbas; Muhammad Jalal Arif (International Journal of Tropical Insect Science, 2026)

Computational discovery of nutritional peptides targeting KEAP1–NRF2 signaling: A novel in-silico strategy to mitigate oxidative stress - Muhammad Arif Asghar; Lifang Zhang; Jianghui Cai; Yazhen Zhang; Bing Wan; Shixin Tang; Lie Yuan; Xiao Zhang; Qinjian Zhao (Trends in Food Science & Technology, 2026)

Biocontrol of powdery mildew in luffa by the silicon-solubilizing endophytic fungi from Trichoderma koningii and Aspergillus clavatus - Asim Ur-Rahman; Sundus Rauf; Khalil Ur Rahman; Mamoona Rauf; Humaira Gul; Alaa Baazeem; Mohamed M. Hassan; Muhammad Hamayun; Muhammad Arif (Physiological and Molecular Plant Pathology, 2026)

Performance of different cushion gases in underground hydrogen storage: Pressure behavior, hydrogen loss, and flow behavior modeling - Haiyang Zhang; Muhammad Arif; Arshad Raza; Mohamed Mahmoud (Gas Science and Engineering, 2026)

Biochar Modification with Iron Oxide Nanoparticles can Enhance its Adsorption Capacity for Phosphorus - Sajeela Sehar; Muhammad Arif; Tanveer Ul Haq; Tanveer Ahmad; Muhammad Farooq Qayyum (Water, Air, & Soil Pollution, 2026)

Multifunctional Greenly Synthesized ZnFe2O4@ZnO Nanocomposites for Photodegradation of Azo Dyes and Antibacterial Applications: Effect of Radical Scavengers and Reaction Parameters - Muhammad Faizan; Muhammad Zahid Ishaque; Yasir Zaman; Abu Bakar Siddique; Muhammad Shahzad; Alia Arif; Hira Zaman (Water, Air, & Soil Pollution, 2026)

Nanoparticles in wheat (Triticum aestivum L) cultivation: a promising solution to alleviate heavy metal toxicity - Eimaan Aamer; Muhammad Saeed; Samia Muhammad Arif; Ghazala Mustafa; Riffat Naseem Malik (Physiology and Molecular Biology of Plants, 2026)

Infectious clone–based dissection of delayed pathogenicity and evolutionary dynamics of Papaya leaf curl Guangdong virus (PaLCuGdV) - Renshu Huang; Muhammad Arif; Amna Saeed; Cheng Song; Omer Beyhan; Muhammed Said Yolcu; Islem Abid (European Journal of Plant Pathology, 2026)
Papaya leaf curl Guangdong virus (PaLCuGdV) is an economically significant begomovirus, although its pathogenicity and evolutionary dynamics are poorly understood. This study involved the construction of a full infectious clone of PaLCuGdV, which was agroinoculated into Nicotiana benthamiana ( N. benthamiana ) to assess the infectivity and symptomatology. The infectious clone elicited typical begomoviral symptoms just at 28 days post-inoculation, signifying delayed pathogenicity. Infection efficiency varied with strain, with successful transmission achieved using Agrobacterium GV301, but not with EHA105 alone. Southern blot analysis confirmed active viral DNA replication solely in diseased plants. Comparative sequencing and recombination analysis identified numerous recombination events among worldwide PaLCuGdV isolates, with the newly defined strain serving as a primary recombinant progenitor. These findings indicate that PaLCuGdV displays delayed symptom expression, strain-specific infectivity, and evolutionary diversity driven by recombination, underscoring the value of infectious clone systems for functional and evolutionary studies of begomoviruses.

Evolution and Biogeography of the Genus Heteropoda (Heteropodinae: Sparassidae) Across Southeast Asia - Shakal Khan Korai; Amir Khan Korai; Shengnan Li; Kamil Kabir; Kamran Haider; Muhammad Raheel Tariq; Arif Ali; Xiaoshan Wang (Zoologica Scripta, 2026)
Heteropoda huntsman spiders are large, fast‐moving predators widely distributed across tropical and subtropical regions, where they function as important nocturnal hunters. Despite their ecological prominence, the evolutionary and biogeographic history of the genus remains poorly resolved. Here, we analysed a six‐locus dataset (two mitochondrial and four nuclear genes) to estimate divergence times and reconstruct ancestral ranges within Heteropoda using Bayesian phylogenetic and statistical biogeographic approaches, and we assessed broad climatic suitability using genus‐level ecological niche modelling. Time‐calibrated analyses support the monophyly of Heteropoda and indicate that crown diversification began during the early Oligocene (~30 Ma; 95% HPD: 18–41 Ma). A primary split between Australasian and Asian lineages is inferred near the Oligocene–Miocene transition (~23 Ma; 95% HPD: 14–33 Ma), followed by radiation within Southeast and East Asia. Ancestral‐area reconstructions consistently recover Australasia as a key ancestral component and suggest repeated dispersal and isolation across the Sunda–Wallacea interface under conditions of long‐term tectonic instability. Ecological niche modelling identifies temperature, precipitation, and elevation as major correlates of climatic suitability, consistent with the predominance of Heteropoda in warm and humid environments. Together, these results provide an integrated temporal, spatial, and ecological framework for understanding diversification and present‐day distribution of Heteropoda across Southeast Asia and adjacent regions.

Nutrient‐Driven Expansion of Reef Fish Habitat Suitability in Indonesian Waters: A 24‐Year Analysis Reveals Iron and Phosphate as Dominant Drivers - Muhammad Arif Nasution; Rika Astuti; Rudi Hermi; Fazril Saputra (Marine Ecology, 2026)
Understanding the environmental factors associated with reef‐associated fish habitat suitability is important for conservation planning in tropical archipelagic systems, where temperature, nutrient dynamics, productivity, and water quality interact across space and time. This study examined temporal changes in predicted habitat suitability for reef‐associated fish across Indonesian waters from 2000 to 2023. Occurrence records were spatially thinned and modeled using MaxEnt with target‐group background selection to reduce sampling bias. Model calibration was performed by comparing regularization multiplier values, and RM = 2 was selected for the final models. Four six‐year periods were analyzed using satellite‐derived oceanographic predictors representing thermal conditions, nutrients, productivity, salinity, dissolved oxygen, and suspended particulate matter. Model performance was consistently good, with mean test AUC values ranging from 0.841 to 0.900. Nutrient‐related and water‐quality variables were the most influential predictors of relative habitat suitability. Suspended particulate matter was the strongest contributor in T1, whereas dissolved iron dominated during T2–T4, followed by phosphate. Temperature variables contributed less than nutrient‐related predictors, suggesting that reef‐associated fish suitability in Indonesian waters is strongly associated with regional biogeochemical and water‐quality gradients. Predicted suitable area showed a non‐linear temporal pattern, declining from T1 to T2 before increasing in T3 and T4. However, these patterns should be interpreted as changes in relative environmental suitability, not direct evidence of population recovery or ecosystem resilience. These findings highlight the importance of integrating water‐quality management, watershed control, reef monitoring, and field validation when using broad‐scale habitat suitability models to inform reef fish conservation in Indonesian waters.

Antihyperuricemia and chemical composition of Boehmeria virgata , in vitro and in silico approach with ADME prediction - Muhammad Ikhlas Arsul; Arif Setiawansyah; Muhamad Insanu; Irda Fidrianny (Natural Product Research, 2026)

Conservation and management implications of genetic and geometric scale variation in the ancient fish giant featherback ( Chitala lopis ) - Boby Muslimin; Gunawan Muhammad; Arif Wibowo; Kurniawan Kurniawan; Vitas Atmadi Prakoso; Rendy Ginanjar; Mochammad Zamroni; Bayu Kreshna Adhitya Sumarto; Septiana Sri Astuti; Deni Irawan; Agus Priyadi; Mirna Dwirastina; et al. (Journal of Fish Biology, 2026)
Giant featherback ( Chitala lopis ) is an ancient species of freshwater fish considered globally extinct until extant populations were re‐discovered in the Sundaland region of Indonesia in 2022. To improve management of the remaining populations, this study used genomic DNA and landmark‐based geometric morphometric analyses of fish scales to evaluate whether these approaches can discriminate among phylogenetic clades, sexes and broad habitat ecotypes inhabited by extant C. lopis populations. DNA analyses of 39 specimens from eight rivers provided the first evidence of two phylogenetic clades: (i) those from Central and South Borneo and (ii) those from West Borneo, Riau, South Sumatra and Jambi. Scale morphology was characterised across eight body areas using scale dimensions (relative height and width to standard length and height‐to‐width ratio), centroid size and Procrustes shape coordinates, with repeated‐measures structure accounted for using linear mixed models and Procrustes ANOVA with a randomised residual permutation procedure (RRPP). Scale dimensions and centroid size varied significantly among body areas (all p p = 0.024), with Clade 2 individuals consistently showing lower values than Clade 1, though scale geometry overall showed limited promise as a rapid non‐destructive stock discriminator. Both clade and sex had small but significant effects on Procrustes scale shape ( R 2 = 0.015 and 0.013, respectively; both p = 0.001), while phenotypic trajectory analysis revealed that males exhibited a significantly greater amplitude of scale shape change across body positions than females (trajectory magnitude: M = 0.289, F = 0.207; p = 0.034), despite both sexes following parallel shape trajectories along the body axis. These results provide a novel morphometric baseline for C. lopis and highlight the importance of body‐position‐specific and multivariate approaches when characterising scale morphology in endangered freshwater fishes.

Changing Water Resources in the Indus Basin: A Multi‐Model Budyko‐Based Analysis - Muhammad Arif; Chia‐Jeng Chen; Nir Krakauer; Tsung‐Yu Lee (International Journal of Climatology, 2026)
Assessing hydroclimatic variability and future water availability is crucial for sustainable water‐resource management. This study utilised the Budyko framework to explore baseline (1962–2005) and projected shifts in the water‐energy distribution across the Indus Basin, including the Upper Indus, Kabul, Jhelum, and Chenab sub‐basins. Future changes in hydroclimatic conditions were assessed using climate projections from multiple models under the RCP4.5 and RCP8.5 scenarios. Our findings highlight significant spatial variability across the Indus sub‐basins: The Upper Indus demonstrated lower evaporative efficiency, whereas Chenab experienced water partitioning primarily through runoff with the highest precipitation. Kabul and Jhelum were more responsive to atmospheric evaporative demand. In both emission scenarios, all sub‐basins showed noticeable changes in the Budyko space over the 21st century, mainly due to warming‐induced increases in potential evapotranspiration, particularly in the Upper Indus and Chenab. The projected directions of these shifts indicate a move towards more energy‐limited hydroclimatic conditions, driven by warming‐induced increases in atmospheric evaporative demand across the Indus sub‐basins. Ensemble projections further indicate increased hydroclimatic variability and greater sensitivity of basin‐scale water distribution to the partitioning between evapotranspiration and runoff under high‐emission scenarios. These results highlight the importance of effective water resource management in the Indus Basin under climate change.

Brown carbon light absorption and radiative forcing: Associations with polycyclic aromatic hydrocarbons in urban northern Taiwan - Ankita Katoch; Yi-Wen Chen; Kuan-Ting Liu; Muhammad Arif; Yu-Hsiang Cheng (Urban Climate, 2026)

Optimization and pilot-scale validation of steam distillation for fresh turmeric essential Oil: Process modelling, bioactive profiling, antibacterial activity, and mass–energy balance - Dodyk Pranowo; Agus Suyono; Sukardi; Muhammad Arif Kamal; Wendra Gandhatyasri Rohmah; Arie Febrianto Mulyadi; Muhammad Hazwan bin Hamzah (Sustainable Chemistry and Pharmacy, 2026)

Parametric optimization and mechanistic investigation of polyvinyl chloride microplastic degradation via an intensified hydrothermal Fenton reaction - Muhammad Zeeshan Gulzar; Guijian Liu; Muhammad Imran; Muhammad Arif; Samina Irshad; Bisma Sattar; Muhammad Irtaza Sajjad Haider; Huihui Zhou; Balal Yousaf (Journal of Water Process Engineering, 2026)

Syzygium cumini-mediated MnO2, Fe3O4 and Mn2FeO4 nanostructures for electrocatalytic water splitting - Fatima Ubaid; Riyadh H. Alshammari; Shabbir Hussain; Muhammad Arif; Muhammad Tariq; Khurram Shahzad Munawar; Asif Ali Tahir (Journal of Environmental Chemical Engineering, 2026)

Identifying industry 5.0 workforce skills for sustainable and human centric transformation: A multi-stakeholder expert panel study in a developing country - Sabeen Malik; Mehreen Malik; Bibi Khadija; Muhammad Arif Nadeem Saqib (Journal of Environmental Management, 2026)

Biochemical Characterization and Phylogenetic Diversity Assessment of Onion (Allium Cepa L.) Genotypes - Samira Habib; Syed Dilnawaz Ahmad Gardezi; Ahmed Mahmoud Ismail; Safira Attacha; Sajid Fiaz; Muhammad Imran Hamza; Armghan Shehzad; Shazia Arif (Plant Molecular Biology Reporter, 2026)

Correction to: A study on using custom 3D-printed tongue bites for radiotherapy patients with oral tongue carcinoma - Muhammad Furqan Zulqurnain; Haris Arif; Misbah Batool; Nouman Amjad; Robin Hill (Physical and Engineering Sciences in Medicine, 2026)

A study on using custom 3D-printed tongue bites for radiotherapy patients with oral tongue carcinoma - Muhammad Furqan Zulqurnain; Haris Arif; Misbah Batool; Nouman Amjad; Robin Hill (Physical and Engineering Sciences in Medicine, 2026)
Oral cavity cancers are a debilitating form of head and neck cancer with high rates of mortality. Radiotherapy is one of the main forms of treatment but relies on minimizing doses that are delivered to organs at risk and considering any motion in the mouth. One solution is to use a block within the mouth which acts to reduce motion and decreases tissue heterogeneity. In this work, we developed a process for designing a customized tissue-equivalent 3D-printed tongue bite and evaluated its impact on the radiation treatment. Six patients with stage III or IV oral cancer were involved. Computed tomography (CT) images for each patient were acquired with currently used Styrofoam tongue bites within the mouth. The designs of 3D tongue bites were prepared using those CT images and then printed on an SLA printer using F80 resin which is a tissue-equivalent and biocompatible material. Secondary CT images were then acquired for each patient with the 3D tongue bites to have a dosimetric comparison. Volumetric-modulated arc therapy (VMAT) planning was carried out for individual patients on both CT images. Plan parameters, fractionation scheme and optimization priorities were all kept the same. The radiotherapy plans utilizing 3D tongue bites showed better PTV coverage and reduced D max ( p = 0.028). Doses to organs at risk (OARs) including brainstem, parotid glands and hard palate were also reduced ( p < 0.028) except for the spinal cord ( p > 0.05). The dose conformity and homogeneity were also improved ( p = 0.028 and p = 0.044 respectively). All patients reported that the 3D tongue bites were soft, conformal to the oral cavity, comfortable and did not cause any gag reflex. We conclude that the 3D tongue bite is a useful utility that improves the treatment of patients with oral cancer.

Green synthesis of silver nanoparticles as a portable colorimetric sensor for mercury detection - Khusna Arif Rakhman; Nurfatimah Sugrah; Lia Destiarti; Khairunnisa A. Sibua; Setyani Dian Puspitasari; Muhammad Hidayat Jaya Miharja; Ni Made Wiratini (Nanotechnology for Environmental Engineering, 2026)

A VMD–PSO hybrid framework with machine and deep learning for Aaccurate spatial–temporal daily rainfall occurrence prediction in Pakistan’s diverse climatic regions - Hira Farman; Muhammad Arif Hussain; Sarang Shaikh; Saif Hassan (Modeling Earth Systems and Environment, 2026)

Irradiation of hexaploid wheat (Triticum aestivum L.) seeds with varying doses of gamma radiation leads to novel mutants - Nasr Ullah Khan; Bareera Tu Nisa; Ihteram Ullah; Douglas Law; Daniel K. Y. Tan; Wael Elmenofy; Mian Abdur Rehman Arif; Muhammad Yasin (Cereal Research Communications, 2026)
The plateauing wheat yield and its narrow genetic diversity warrants modifying wheat to meet the global food demand from the growing population. Gamma radiation-based mutagenesis is a widely used technique to develop or improve crops like wheat. However, optimizing radiation dose level and the response of wheat genetic background to radiation dose are the two key challenges. This study was conducted to assess the effect of different gamma radiations doses (0 Gy, 100 Gy, 150 Gy, 200 Gy and 250 Gy) on early growth, development and yield related attributes of six wheat genotypes (AZRC Dera, RK2022, landrace-49, landrace-52, black wheat and Kashmiri landrace), and to screen out mutants with promising growth, developmental and yield related attributes. Eighteen different traits (early growth, phenology and yield of the wild type and M 1 mutants) of the six wheat genotypes revealed differences ( p < 0.01) among genotypes (wheat) and treatment (gamma radiation doses), underscoring the genetic diversity and differential radio-sensitivity of the wheat genotypes. Additionally, all the eighteen traits among all genotypes were negatively ( p < 0.01) affected at high dose of 250 Gy, while optimum dose of 150 Gy positively impacted early growth and yield related traits. Kashmiri landrace exhibited improved superior yield related attributes such as early maturity, longer spike, greater spikelets per spike, greater number of seeds per spike and superior seed weight per spike, making it an ideal genetic material for mutation breeding programs. Hierarchical clustering revealed five distinct clusters of genotypes, Kashmir landrace and black wheat being the most distinct genotypes. Gamma radiation mutagenesis produced a vast array of radio morphs such as double spikes per tiller, high tillering, dwarfing and altered spike architecture. These mutants provide novel and valuable genetic resources for wheat breeding.

In situ biotransformation of synthetic glutamate to γ-amino butyric acid by an auxotrophic Lactococcus lactis in polysorbate-mediated thermoaerobic process - Siaknder Ali; Kinza Arif; Qaiser Farid Khan; Muhammad Usman Ahmad; Ifrah Shabbir; Iram Liaqat; Tawaf Ali Shah; Gehan M. Elossaily; Yousef A. Bin Jardan (Biodegradation, 2026)

A PRISMA-based systematic review on future marine antifouling bioagents: Bioprospecting insights from corals and algae and ship hydrodynamic - Teguh Purnomo; Muhammad Arif Budiyanto; Yasman (Marine Pollution Bulletin, 2026)

Recent advances in structural damage assessment methods for ship collisions: A critical review of experimental, numerical, and analytical approaches - Abid Paripurna Fuadi; Muhammad Arif Budiyanto; Sunaryo; Achmad Riadi; Teguh Muttaqie; Xueqian Zhou (Ocean Engineering, 2026)

Influencing factors and prediction of CO2 wettability in coal seams for carbon geo-storage: leveraging data-driven machine learning approaches - Andreas Fernandez-Moncada; Muhammad Arif (Fuel, 2026)

Evaluating Lemna minor for bioethanol production and bioremediation of petrochemical wastewater - Fozia Shafiq; Ihsan ud din; Arif Ali Khattak; Muhammad Afzal (Biomass and Bioenergy, 2026)

Evolutionary insight and characterization of WOX genes in callus development and differentiation of Peucedanum praeruptorum - Cheng Song; Haoyu Pan; Muhammad Arif; Haiyu Wang; Yunpeng Cao; Bangxing Han; Muhammad Aamir Manzoor (Planta, 2026)

Multi-epitope vaccine design against Nipah virus: An immunoinformatics approach targeting South and Southeast Asia populations - Moh. Royhan Afnani; Viol Dhea Kharisma; Aswin Rafif Khairullah; Abdugani Abdurasulov; Roza Abdyldayeva; Maksim Rebezov; Arli Aditya Parikesit; Vikash Jakhmola; Rollando Rollando; Arif Nur Muhammad Ansori (In Silico Pharmacology, 2026)

Micro-CT based observations of pore structure in tight sandstone and residual oil under CO2 and water flooding - Sisi Chen; Hongyan Yu; Wangyikun Fan; Muhammad Arif (Fuel, 2026)

Individual and combined decontamination effect of aqueous ozone and plant extracts on fungi and aflatoxins in brown rice - Iqra Naeem; Amir Ismail; Yun Yun Gong; Muhammad Riaz; Muhammad Arif Shahzad; Aneela Hameed; Mubashir Aziz; Asif Mahmood; Waheed Al Masry; Muhammad Latif; Sher Ali; Carlos A.F. Oliveira (Food Control, 2026)

Synergistic photo-assisted AOPs using acid-modified biochar: Enhanced micropollutant levofloxacin degradation in industrial wastewater - Muhammad Irtaza Sajjad Haider; Guijian Liu; Balal Yousaf; Muhammad Arif; Kiran Aziz; Bisma Sattar; Muhammad Zeeshan Gulzar; Hameer Chand; Ruijia Liu (Desalination, 2026)

Biotechnological and nutraceutical evaluation of Boehmeria virgata root extract: Phytochemical profiling, antidiabetic bioactivity, and safety assessment - Haeria Doloking; Andi Andriani Musfar; Rahmi Fitri Lestari Jamal; Riska Yuniarti; Ainun Sakinah; Fitri Sea Febriani; Akmal Zulfi; Arif Setiawansyah; Muhammad Ikhlas Arsul; Alwiyah Nur Syarif; Muhammad Ikhwan Arsul (Biocatalysis and Agricultural Biotechnology, 2026)

Remediation of Pb2+ Ions by Green Route Modified Carbon Nanotubes - Saba Zafar; Abdul Amir; Saira Arif; Fozia Bibi; Ammara Aftab; Muhammad Naeem Ahmed; Muhammad Waseem (Water, Air, & Soil Pollution, 2026)

A Practical Framework for Mangrove Rehabilitation Sites Selection Using Scalable Biophysical Indicators - Bayu Prayudha; Yaya I. Ulumuddin; Suyadi Suyadi; Suyarso Suyarso; Arif Seno Adjie; Udhi E. Hernawan; Muhammad R. Ramadhani (International Journal of Environmental Research, 2026)

Integrated computational, pharmacological and molecular investigations of piperitone in mitigating Alzheimer disease pathology by targeting cholinesterases, β-secretase and neuroinflammation - Rubia Anwer; Ihsan Ullah; Arif-ullah Khan; Mushtaq Ahmad Mir; Nasreena Bashir; Syed Uzair Ali Shah; Muhammad Ayaz (Inflammopharmacology, 2026)

Mineral chemistry and alteration characteristics of sulfide-bearing metavolcanics in the Thalle area, Kohistan–Ladakh Arc: insights into magmatic-hydrothermal fluid evolution - Muhammad Farhan; Tehseen Zafar; Mohammad Arif; Chun-Feng Li; Zahid Hussain; Zaheen Ullah; Syed Wajid Hanif Bukhari; Uzair Siddique; Syed Ali Turab; Mubasir Ali (Geosciences Journal, 2026)

mcr gene family evolution and structural mechanisms of colistin resistance: from mcr-1 to emerging variants - Muhammad Shahid Mehmood; Uthpala Kavindi Rupasinghe Koggala Marakkalage; Tabish Arif; Fariha Javaid; Muhammad Ali Abid; Muntha Shahid; Anwar Parvez; Muhammad Nabeel Saddique; Sultan Ali (Archives of Microbiology, 2026)

Pharmacological investigation of natural compounds for therapeutic potential in neuropathic pain - Muhammad Faheem; Arif-ullah Khan; Fawad Ali Shah (Natural Product Research, 2026)

Effect of Nitrogen and Maize Straw on Soil Nitrogen Transformation, Farm Profitability, and Wheat Yield: Balancing Productivity and Environmental Sustainability - Siddique Ahmad; Wenjing Song; Yanling Mu; Xiaobin Zhang; Shuping Xiong; Muhammad Arif; Muhammad Amjad; Laiba Urooj; Basit Ullah; Xinming Ma; Yihao Wei (Agricultural Research, 2026)

Quantitative analysis and toxicological mechanisms of various male infertility inducers: A network meta-analysis and pharmacological approach - Muhammad Arif Asghar; Ao Zhang; Shixin Tang; Hang Han; Bing Wan; Jingwei Wu; Li Ping Wong; Xiao Zhang; Qinjian Zhao (Reproductive Toxicology, 2026)

Sulfur–regolith composite material for radiation shielding on Mars: A sustainable ISRU approach - Muhammad Nazrif Zamani; Norhazilan Md Noor; Sarehati Umar; Mohamad Shazwan Ahmad Shah; Muhammad Syahir Sarkawi; Asyraf Arif Abu Bakar; Nur Hafizah A. Khalid; Hanis Hazirah Arifin (Journal of Cleaner Production, 2026)

Advanced fabrication strategies for Durable, High-Efficiency, and scalable solid oxide fuel cells - Abid Ullah; Shahbaz Ahmad; Tahir Ali; Ayesha Samreen; Saim Saher; Muhammad Zulqarnain Arif; Arunachala M. Kannan (Fuel, 2026)

Combining anxiolytic activity of thymol and trans-ferulic acid: a potential GABAergic intervention - Md. Hanif Munshi; Noshin Tasnim Yana; Imam Hossen Rakib; Emon Mia; Nusrat Jahan Tohfa; Md. Sakib Al Hasan; Md Abu Sayeed; Mst. Sumaia Akter; Md. Arif Hossain; Muhammad Torequl Islam; Md. Shimul Bhuia; Mushtaq Ahmad Ansari (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Sustainable Management Practices for Maximizing Productivity and Quality in Dual-Purpose Cereal Systems - Maaz Khan; Muhammad Arif; Fazal Munsif; Nazir Ahmad Khan; Muhammad Mehran Anjum; Mehran Ali (International Journal of Plant Production, 2026)

Molecular evaluation of superior agronomic traits in local wheat germplasm using functional markers - Muhammad Qamar Ashfaq; Andleeb Anjum Qazalbash; Tayyaba Shaheen; Arzish Javaid; M. Qandeel Waheed; Anjuman Arif (Genetic Resources and Crop Evolution, 2026)

Interface synergistic-driven electronic modulation in amorphous CoFeB@g-C3N4 for high-performance bifunctional OER/HER electrocatalysis - Abdul Haq; Anuj Kumar; Muhammad Arif; Umair Azhar; Huma Ahmad; Unaiza Talib; Mahnoor Ahmed; Muhammad Asim Mushtaq; Muhammad Sagir; Muhammad Faheem Maqsood; Kumar Venkatesan; Ghulam Yasin (Journal of Environmental Chemical Engineering, 2026)

Water hyacinth-derived cellulose biocomposites: Extraction methods, physicomechanical properties, and sustainable applications — A review - Vasi Uddin Siddiqui; Azrol Jailani; Abdul Habib; M. Hazim Hidzer; Farah Usmani; Muhammad Adlan Azka; Muhammad Irfan Suffian; Muhammad Arif Saifulazmi; S.M. Sapuan; Melbi Mahardika; Kadriadi; Hairul Abral (Biomass and Bioenergy, 2026)

A comprehensive risk assessment of non-dioxin-like and dioxin-like PCBs in indoor and outdoor dust from Hefei, China - Mengchen Shen; Li Zhou; Guijian Liu; Ruijia Liu; Hao Yin; Yanyun Hu; Muhammad Arif; Qing Zhang (Atmospheric Environment, 2026)

Aspergillus flavus and Colpomina sinousa mixture act as biocatalyst to improve growth, fruit yield and salinity resistance of Brassica napus for sustainable agriculture - Hira Wahid; Humaira Gul; Mamoona Rauf; Asma Tabassum; Aliya Rehman; Muhammad Arif; Muhammad Hamayun; Hatem E. Semary; Zainul Abideen (Biocatalysis and Agricultural Biotechnology, 2026)

Developing a RUSLE-Based Tool for Analyzing Climate Induced Soil Erosion and Reservoir Sedimentation in the Tarbela Region - Muhammad Arif Goheer; Sher Shah Hassan; Syeda Rosheen Raza Kazmi; Muhammad Taimoor Ashfaq Malik; Syed Zee Ali Shan (International Journal of Environmental Research, 2026)

Native Plants as Living Sensors: Tracking Air Pollution in Industrial Zones - Muhammad Sharif; Ummar Iqbal; Abdul Wahab; Muhammad Yousuf; Mehboob Ahmad; Muhammad Sharjeel Arif (International Journal of Environmental Research, 2026)

Effectiveness of treatments for propranolol toxicity: a systematic review of current approaches and evidence - Yafei Hu; Khizra Mujahid; Awais Ahsan; Anika Fatima; Inza; Maham Maqsood Ahmed; Maham Anoosh Butt; Sadia Younas; Muhammad Arif Aslam; Hafiz Muhammad Ahmad Javaid (European Journal of Clinical Pharmacology, 2026)

Analysis of multiple blockages in a coolant channel of IAEA research reactor using CFD - Muhammad Abdullah; Muhammad Nadeem; Arif; Adnan Hamid (Annals of Nuclear Energy, 2026)

Machine learning-guided discovery of mitogen-activated protein kinase 7 (MAPK7 inhibitors): integrating virtual screening, docking, and molecular dynamics simulations - Chandni Hayat; Amar Ajmal; Nayab Gul; Muhammad Numan; Haleema Bibi; Naveed Akhtar; Laiba Sultan; Arif Ali; Muhammad Tahir Khan; Muhammad Saqib (In Silico Pharmacology, 2026)

Carbon-based materials for photocatalytic degradation of pharmaceuticals and drugs - Shan Arif; Sufian Rasheed; Naseer Ahmad; Muhammad Ikram Nabeel; Waqas Ahmad; Thamer Alomayri; Dilshad Hussain; Syed Ghulam Musharraf (Journal of Water Process Engineering, 2026)

Mild acid batch conversion of corncob biomass to furfural: Toward circular bioenergy and global research trends - Dita Ariyanti; Misri Gozan; Chintya Komala Sari; Roni Maryana; Dino Rimantho; Okri Asfino Putra; Lisnawati; Leny Yuliatun; Muhammad Iqbal Maulana; Jumina; Sri Fiviyanti; Muhammad Hamzah Fansuri; et al. (Bioresource Technology, 2026)

Assessment of Chromium Toxicity and Health Risk in Vegetables Grown in Municipal Solid Waste-Amended Soils - Asma Ashfaq; Zafar Iqbal Khan; Toqeer Abbas; Saima Sadaf; Muhammad Arif; Muhammad Fayyaz; Iqra Parvez (Water, Air, & Soil Pollution, 2026)

Development of a Novel Pan-Species Multi-Epitope Vaccine (PS-MEV) Targeting Nine Staphylococcus Species to Combat Antibiotic Resistance - Allah Rakha Yaseen; Muhammad Suleman; Mahnoor Habib; Tehreem Arshad; Muskan Fatima; Ayesha Arif; Hafiza Sadia Rasool (Probiotics and Antimicrobial Proteins, 2026)

Wheat SLC25A4-7B negatively regulates drought tolerance by coordinating stomatal aperture size and abscisic acid content - Jie Tian; Pengpeng Zhao; Dingli Hong; Zhongni Wang; Muhammad Arif; Chang An; Ling Xu; Mingjian Ren; Luhua Li; Ruhong Xu (Planta, 2026)

Pathogenic CDKN2A germline variants are rare in a cohort of unselected pancreatic cancer patients from Pakistan - Shumaila Arif; Noor Muhammad; Humaira Naeemi; Muhammad Usman Rashid (Familial Cancer, 2025)

Halotolerant PGPRs attenuate salinity stress in maize through differential expression of stress-related genes and regulated Na+/K+ homeostasis - Tahira Yasmeen; Muhammad Saleem Arif; Aqeel Ahmad; Muhammad Usman; Mohsin Tariq; Waqas Haider; Afira Syrish (South African Journal of Botany, 2025)

Optimizing lead-acid battery sizing for household UPS systems under variable power outages - Ihtesham Ahmad; Shahbaz Ahmad; Muhammad Zulqarnain Arif (Next Research, 2025)

First-principles study on structural, elastic, acoustic and optoelectronic properties of hexagonal magnesium oxide (MgO) - Maryam Tariq; Tariq Mahmood; Robina Ashraf; Imran Aslam; Muhammad Rizwan; Arbab Arif; Ch. Omer Javed; Afshan Urooj (Next Research, 2025)

Protein-based functional materials for gold ion separation: Mechanisms, challenges and future perspectives - Qingmin Yang; Yingying Zhang; Yuanhang Yang; Xiaoyun Zhang; Yongliang Ding; Arif Muhammad; Guichen Liu; Facui Yang; Renyuan Song; Yanfang Tai; Peng Yang; Jian Zhao (Journal of Environmental Chemical Engineering, 2025)

Tunable photocatalytic activity of metal oxides: designing, principles, parameters, and progress - Muhammad Arif (Journal of Environmental Management, 2025)

Wettability of hydrogen-rock-brine systems: Parametric analysis and knowledge gaps - Ahmed Adila; Mahmoud Aboushanab; Arshad Raza; Mohamed Mahmoud; Stefan Iglauer; Ryan T. Armstrong; Muhammad Arif (Fuel, 2025)

Impact of post-harvest process and methanol polarity on the content of niazirin, flavonoids, phenols, and antioxidant activity index of Moringa oleifera Lam leaves - Arif Setiawansyah; Bella Fiolita; Sandra Agatha; Rina SE Sitindaon; Muhammad Andre Reynaldi; Lalu Husnul Hidayat; Ismanurrahman Hadi; Lina Permatasari; Nurul Hidayati; Muhammad Ikhlas Arsul; Septriyanto Dirgantara (Food and Humanity, 2025)

Hemoglobin-mediated synthesis of iron-hybridized gold nanoclusters for colorimetric biosensing and antibacterial wound therapy - Aisha Kanwal; Juanhua Tian; Qingyue Yang; Yixiang Chen; Arif Muhammad; Khian-Hooi Chew; Zihao Li; Zhongli Lei; Peng Yang; Hao Ren (Chemical Engineering Journal, 2025)

Sustainable biodiesel production via Alkanna tinctoria oil Conversion: A multi-method modeling approach utilizing crab shell-derived biochar catalysts - Ali Hamid; Hammad Khan; Arsalan Arif; Muhammad Arshad; Sajjad Hussain; Arslan Maqbool (Biomass and Bioenergy, 2025)

Incidence and Molecular Characterization of Tobacco Rattle Virus (TRV) in Azad Jammu and Kashmir-Northeast of Pakistan - Nayla Haneef; Muhammad Arif; Asad Ali; Muhammad Tariq Khan (Potato Research, 2025)

Micro-scale Two-Phase Flow Experiments and Residual Oil Distribution in Tight Sandstone - Wangyikun Fan; Hongyan Yu; Shanbin He; Jianchao Shi; Jiahao Wang; Muhammad Arif; Chenchen Wang; Shuaiwei Ding; Yihuai Zhang (Natural Resources Research, 2025)

Time-dependent regulation of ABA and JA in starch accumulation during the natural development of GZ 1 grains - Ling Xu; Yunhao Deng; Guifen Wei; Muhammad Arif; Zhongni Wang; Ruhong Xu; Luhua Li (Molecular Biology Reports, 2025)

Engineering high yield basmati rice by editing multiple negative regulators of yield - Muhammad Abu Bakar Waqas; Muhammad Jawad Akbar Awan; Imran Amin; Muhammad Arif; Zahid Mukhtar; Shahid Mansoor (Molecular Biology Reports, 2025)

Activation function impact on rainfall prediction: comparative insights across ML and DL architectures - Hira Farman; Muhammad Arif Hussain; Saif Hassan; Sarang Shaikh; Khurshed Ali (Modeling Earth Systems and Environment, 2025)
Rainfall prediction is critical in agriculture, water resource management, transportation, and disaster planning. As a critical component of the hydrological cycle, precisely forecasting daily rainfall helps to lessen the effects of floods, droughts, and other extreme weather events. However, due to the nonlinear and complicated interaction of meteorological factors, daily rainfall forecast remains a grim problem. The proposed work adopts a systematic deep learning-based framework, integrating Long Short-Term Memory (LSTM) and Bidirectional LSTM (BiLSTM) models and Transformers to predict the rainfall of the next day. Besides deep models, a few machine learning classifiers, such as the Logistic Regression (LR), Support Vector Machines (SVM), and the K-Nearest Neighbor (KNN) will be applied to benchmark the performance.One of the main insights in this study is the systematic comparison of a wide variety of activation functions, such as Sigmoid, ReLU, Tanh, Swish, Leaky ReLU, and ELU to measure their effects on model accuracy, convergence, and generalization performance. An experiment was employed on real-life rainfall of the USA dataset, which proved the efficiency of using the BiLSTM model and ReLU and Leaky ReLU activation functions to achieve up to 99% accuracy, whereas Transformer model was also efficient as it obtain up to 98%, but it was not stable and showed a tendency towards occasional instability during the training process. On the contrary, traditional machine learning models displayed an intermediate predictive accuracy, with average accuracies of approximately 87%. Significantly, the results were validated through multi-seed experiments with confidence intervals and baseline benchmarks, demonstrating that the near-perfect scores were not incidental but consistently stable across different initializations. This study provides a new theoretical standpoint in terms of activation functions in deep sequence models as it studies beneficiaries and shortcomings through a mathematical point of view. The results highlight that activation function selection can have an important impact on the accuracy of forecasts and can be significant in building more accurate, scalable, and general learning subroutines in weather predictions.

Superior performance of triticale over wheat, barley, and oat under grazing and cutting for dual-purpose technology in warmer and colder northern regions - Maaz Khan; Muhammad Arif; Fazal Munsif; Nazir Ahmad Khan (Journal of Crop Science and Biotechnology, 2025)

Green Synthesis of Mangifera Indica Mediated NiO and NiMn2O4 Nanomaterials for Electrocatalytic Water Splitting - Fatima Masood; Shabbir Hussain; Muhammad Arif; Shahzad Murtaza; Muhammad Imran; Muhammad Bilal Tahir; Khurram Shahzad Munawar; Hamad M. Alkahtani; Amer Alhaj Zen; Syed Adnan Ali Shah (International Journal of Environmental Research, 2025)

Switching on survival: how rice outsmarts heat with a natural gene circuit - Mohammad Abubakar Yasin; Muhammad Waseem Sajjad; Rubab Zahra Naqvi; Imran Amin; Muhammad Arif (Functional & Integrative Genomics, 2025)

Microbial Proteases: Integration into Food Products and Industrial Processes - Gad Elsayed Mohamed Salem; Muhammad Arif; Imad A. Idris; Mohamed A. El-Sakhawy; Suchana Chavanich; Waleed Alahmad; Yuanzhang Zheng; El-Sayed Salama (Current Microbiology, 2025)

Genomic Insights into Poultry-Associated Staphylococcus Aureus from Haripur, Pakistan - Arif Ullah; Bushra Fatima; Mohammad Ejaz; Muhammad Ali Syed (Current Microbiology, 2025)

FT-IR-based fingerprint combined with unsupervised chemometric analysis revealed particle sizes and aqueous-ethanol ratio alter the chemical composition and nutraceutical value of Daucus carota - Arif Setiawansyah; Arum Trisna Widiyawati; Masrukah Septi Dinika Sari; Muhammad Andre Reynaldi; Nurul Hidayati; Reza Alrayan; Septiawan Adi Nugroho (Natural Product Research, 2025)

Paleoenvironmental and organic facies analysis of potential hydrocarbon source rocks in Surghar Range, Kohat Plateau - Arif Nazir; Fraz Khalid; Saeed Abbas; Muhammad Deen; Munawar Iqbal; Umer Younas; Muhammad Iftikhar Khan; Rab Nawaz (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Assessing a strategy to recover trehalulose sugar from stingless bee honey Geniotrigona thoracica sp. via cation exchange adsorption - Muhammad Hairul Ridzwan; Zurina Zainal Abidin; Norhasnida Zawawi; Arif Zaidi Jusoh (Food Chemistry, 2025)

High-performance clay and K2CO3-Modified sludge biochar for efficient reactive black-5 Removal: Mechanistic insights and alleviation of phytotoxicity - Muhammad Arif; Guijian Liu; Muhammad Zia-ur-Rehman; Qumber Abbas; Aniqa Ashraf; Muhammad Saqib Rashid; Krzysztof Pikon; Balal Yousaf (Biomass and Bioenergy, 2025)

Effect of high-ratio co-firing of Samanea saman wood with low-rank coal on slagging, fouling, and ash-related problems in a drop tube furnace - Suyatno Suyatno; Hafizh Ghazidin; Ade Sana Ruhiyat; Fairuz Milkiy Kuswa; Feri Karuana; Prabowo Prabowo; Arif Darmawan; Kusdi Prijono; Tata Sutardi; Kusmiyati Kusmiyati; Achmad Nurfanani; Hanggi Eko Samudra; et al. (Biomass and Bioenergy, 2025)

Bcl-2-Associated Athanogene (BAG) Co-chaperones: Key Players in Multiple Abiotic and Biotic Stress Tolerance in Plants - Muhammad Arif; Shuzhen Men; Ayesha Fazal Nawaz; Xin Li; Ling Xu; Xuemin Yang; Shah Fahad; Parvaiz Ahmad; Ruhong Xu; Luhua Li (Journal of Plant Growth Regulation, 2025)

PM2.5 pollution and its correlation with meteorological parameters over the four capital cities of Pakistan - Bahadar Zeb; Jawad Nasir; Khan Alam; Allah Ditta; Muhammad Arif Aman; Muhammad Shafiq (Environmental Monitoring and Assessment, 2025)

4-Propyl- and 4-phenylcoumarins from mesua lepidota T. Anderson and their cytotoxic activity - Mulyadi Tanjung; Muhammad Fajar Aldin; Noviani Nurma Arif; Ratih Dewi Saputri; Norizan Ahmat; Tjitjik Srie Tjahjandarie (Natural Product Research, 2025)

Functionalized biochar with enhanced interfacial properties for synergistic adsorption and photodegradation mechanisms of levofloxacin in industrial effluents - Muhammad Irtaza Sajjad Haider; Guijian Liu; Balal Yousaf; Muhammad Arif; Aniqa Ashraf; Rabia Safeer; Samra Ijaz; Ruijia Liu (Process Safety and Environmental Protection, 2025)

Optimization of anaerobic wastewater effluent for efficient microalgal growth and biomacromolecules production: Lab-scale photobioreactor and machine learning performance - Muhammad Arif; Mabkhoot Alsaiari; Mohammed Jalalah; Farid A. Harraz; Nahla S. Zidan; Roba Alatawy; El-Sayed Salama (Journal of Environmental Chemical Engineering, 2025)

Sustainable rhenium adsorption and separation from molybdenum-containing solution using soy protein-based material - Muhammad Arif; Qingmin Yang; Aisha Kanwal; Jian Zhao; Mohsan Nawaz; Peng Yang; Hao Ren (Journal of Environmental Chemical Engineering, 2025)

Thermodynamics and kinetics of water vapor adsorption in isolated kerogen: Evidence from experiments and molecular dynamics simulations - Zhikai Liang; Zhenxue Jiang; Zhuo Li; Yihuai Zhang; Shijie Ma; Muhammad Arif (Gas Science and Engineering, 2025)

Retraction notice to “Sustainable, economical and rapid treatment of multiple lung diseases using therapeutic potential of curcumin nanoparticles” [Environ. Res. 233 (2023) 116477] - Qudsia Kanwal; Samiah Shahid; Abeel Ahmad; Arif Nazir; Muhammad Yasir; Aneela Anwar; Samar Z. Alshawwa; Munawar Iqbal (Environmental Research, 2025)

Genetic Enhancement of Sugar Recovery Percentage in Commercial Sugarcane by Inducing Sweet Sucrose Isomerase Gene III (SSGIII) - Mudassar Fareed Awan; Usman Arif; Muhammad Farhan Sarwar; Momna Toqeer Dar; Safia Obaidur Rab (Sugar Tech, 2025)

Retraction notice to “Template-based textural modifications of polymeric graphitic carbon nitrides towards waste water treatment” [Chemosphere 302, September 2022,134792] - Umair Azhar; Muhammad Sohail Bashir; Muhammad Babar; Muhammad Arif; Afaq Hassan; Asim Riaz; Rana Mujahid; Muhammad Sagir; Saadat Ullah Khan Suri; Pau Loke Show; Jo-Shu Chang; Kuan Shiong Khoo; et al. (Chemosphere, 2025)

Sedimentary architecture of the ediacaran mixed carbonate-siliciclastic system, NW arabian plate: Regionally extensive marine incursion or syntectonic fault-controlled basin? - Muhammad Hammad Malik; Arif Hussain; Ardiansyah Koeshidayatullah; Justin V. Strauss; Adhipa Herlambang; Abdulwahab M. Bello; Khalid Al-Ramadan (Precambrian Research, 2025)

Variations in the compositional profile of polycyclic aromatic moieties in coals from Bara, Patala and Salt Range formations: Insights into the mechanisms affecting the sedimentary record - Arif Nazir; Qaiser Hussain; Saeed Abbas; Fraz Khalid; Muhammad Deen; Abid Ali; Munawar Iqbal (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Impact of petrophysical properties on CO2 residual trapping in limestone formations - Johny Mouallem; Arshad Raza; Mohamed Mahmoud; Joseph Mouallem; Muhammad Arif (Fuel, 2025)

Evolution of water vapor adsorption behavior on kerogen: Pyrolysis and molecular investigation - Zhikai Liang; Zhenxue Jiang; Zixin Xue; Ruihua Chen; Hailong Yu; Muhammad Arif (Fuel, 2025)

Ultrahigh dielectric tunability at low voltage in PVDF nanocomposite driven by nonlinear ZnO-ferroelectric core-shell architecture for microwave device application - Arif Hussain; Suibin Luo; Can Zhao; Jie Liu; Asad Muhammad Khan; Shuhui Yu (Chemical Engineering Journal, 2025)

Epidemiology of Lumpy Skin Disease virus in large ruminants of Potohar region, Pakistan - Gohar Khadim; Aamer A. Shah; Aayesha Riaz; Arfan Yousaf; Mahwish Ali; Mian Muhammad Awais; Muhammad Arif Zafar; Bakhtawar Khadim; Nimra Riaz (Tropical Animal Health and Production, 2025)

Mitigating Terminal Drought in Chickpea (Cicer arietinum L.) Using Organic Manures; Effects on Yield, Potassium Uptake and Antioxidants Activity - Malik Muhammad Yousaf; Azra Yasmeen; Shadia Hama Salih Kareem; Muhammad Arif; Hesham F. Alharby; Hameed Alsamadany; Yahya M. Alzahrani; Amnah M. Alamri; Ammara Latif; Hafeez ur Rehman (International Journal of Plant Production, 2025)

Engineered macrophages as versatile platforms for targeted cancer immunotherapy - Khizra Mujahid; Muhammad Arif Aslam; Jutaek Nam; Jeong Uk Choi (Journal of Pharmaceutical Investigation, 2025)

Synthesis, Spectroscopic, Electronic and Molecular Docking Studies of Pyrazole Based Chalcones as Potential Anticancer Agents - Noreen Aslam; Muhammad Ibrahim; Afifa Yousuf; Muhammad Arif Ali; Jonathan M. White; Ansa Madeeha Zafar; Mussarat Jabeen; Misbahul Ain Khan (Journal of Fluorescence, 2025)

DusVax: a universal pan-viral multi-epitope vaccine (PV-MEV) for pandemic preparedness against ten high-priority viral pathogens - Allah Rakha Yaseen; Muhammad Suleman; Mahrukh Afzal; Hania Usama; Warda Ashfaq; Sehrish Firyal; Ayesha Arif; Amna Latif; Ali Asghar; Abdul Salam Qadri (The Nucleus, 2025)

Microplastic contamination in agricultural soils from mulch films and organic amendments: Transformation mechanism, soil-Biota toxicity, and future perspectives - Bisma Sattar; Guijian Liu; Balal Yousaf; Muhammad Arif; Muhammad Zeeshan Gulzar; Muhammad Irtaza Sajjad Haider; Rabia Safeer; Samra Ijaz; Muhammad Awais Haider; Kiran Aziz (Waste Management, 2025)

Recent advances in nanocatalysis for clean energy and carbon neutral applications - Jamshaid Rashid; Ayesha Arif; Pir Muhammad; Ming Xu; Rajeev Kumar (Fuel, 2025)

Dew Water Production Evaluation Using a Mini Portable Dew Water Harvesting Unit Operated Under the Thermoelectric Cooling (TEC) Varied Voltages in Malaysia - Muhd Hazwan Hisyam Bin Abu Hassan; Mohd Remy Rozainy Mohd Arif Zainol; Chang Chun Kiat; Ali Riahi; Muhammad Khairi A.Wahab (Water Conservation Science and Engineering, 2025)

Evaluating the impacts of environmental stresses on agriculture in the context of climate resilience - Muhammad Arif; Sajid Fiaz; W. M. W. W. Kandegama; Sujitraj Sheth; Luhua Li (Plant Molecular Biology, 2025)

Exploring the propagation characteristics from meteorological to hydrological drought across diverse climate regions in the upper Indus Basin, Pakistan - Arif Hussain; Jianxia Chang; Azfar Hussain; Zhou Kai; Guibin Yang; Muhammad Saifullah (Natural Hazards, 2025)

Green-Synthesized ZnO Nanoparticles Using Methanolic Extract of Moringa oleifera Leaves: Characterization and Evaluation of Wound Healing Efficacy - Mazhar Abbas; Aqsa Mumtaz; Osama A. Mohammed; Kinza Zafar; Ishtiaq Ahmed; Muhammad T. Iqbal; Munawar Iqbal; Arif Nazir; Ali M. S. Eleragi; Lobna A. Saleh; Mohammed A. Attia; Emad Bahashwan; et al. (Journal of Pharmaceutical Innovation, 2025)

Anthropogenic dust pollution influences leaf and root morpho-anatomical traits by altering the metabolism and biochemical properties of indigenous vegetation - Muhammad Asim Sultan; Iftikhar Ahmad; Muhammad Arif; Saima Sadaf; Muhammad Kamran; Toqeer Abbas; Shifa Shaffique; Mansour K. Gatasheh (Environmental Geochemistry and Health, 2025)

Combination of Sargassum wightii extract and pyridoxin mixture improves growth and salinity tolerance in Okra for sustainable agriculture - Zawar Khan; Humaira Gul; Aliya Rehman; Asma Tabassum; Mamoona Rauf; Muhammad Arif; Muhammad Hamayun; Mohamed A. El-Sheikh; Zainul Abideen (Algal Research, 2025)

Platelet-Rich Plasma (PRP) Mitigates Kidney Dysfunction in Alloxan-Induced Diabetic Mice via Modulation of Renal Iron Regulatory Genes - Humaira Allay Ali; Muddasir Hassan Abbasi; Tasleem Akhtar; Amin Arif; Mehreen Anjum; Sana Fatima; Rabia Mehmood; Adil Farooq; Nadeem Sheikh; Muhammad Babar Khawar (Biochemical Genetics, 2025)

How shallow solum shapes plant selection, tree diversity, carbon stocks and earthworms in coffee agroforestry - Rika Ratna Sari; Muhammad Naufal Ramadhan; Nadiyah Rifdatun Nailah; Nanda Ardiansyah; Ahmad Ali Yuddin Fitra; Arif Firmansyah; Rizki Maulana Ishaq; Danny Dwi Saputra (Agroforestry Systems, 2025)

Selecting the best CMIP6 GCMs for application and downscaling studies over Pakistan, Nepal and Bangladesh - Shaukat Ali; Michelle Simões Reboita; Zulfiqar A. Bhutta; Muhammad Arif Goheer; Joao Gabriel Martins Ribeiro; Christie André de Souza; Glauber Willian Ferreira; Jai Das; Rida S. Kiani; Azfar Hussain; Fatima Saeed; Muhammad Adnan Abid; et al. (Acta Geophysica, 2025)

Determination of heavy metals and morphoanatomical characteristics of the monocots Aristida mutabilis and Cenchrus ciliaris in the dust-contaminated stone crushing industry of Sargodha, Pakistan - Muhammad Asim Sultan; Iftikhar Ahmad; Muhammad Arif; Saud Alamri; Manzer H Siddiqui; Saima Sadaf; Muhammd Kamran (Environmental Monitoring and Assessment, 2025)

Hospitality and tourism trends drive spatial shifts in urban service accessibility - Ye Ai; Mengyao Tian; Zhangting Chen; Muhammad Arif (Sustainable Cities and Society, 2025)

Novel and recyclable Ca(OH)2 and Mg(OH)2 modified amberlyst-15 for selective removal of heavy metal ions - Mishal Batool; Amna Mehmood; Saira Arif; Muhammad Jalal; Farooq Ahmad; Muhammad Waseem (Process Safety and Environmental Protection, 2025)

Effect of pretreatment methods of Kabuli chickpea on microstructure and physical properties of enriched bread - Obasi Ukpai Ukoji; Muhammad Mudassir Arif Chaudhry; Lindsey Boyd; Elaine Sopiwnyk; Michael T. Nickerson; Jitendra Paliwal (Food Structure, 2025)

Mapping mangroves land suitability using machine learning and MCDM in the Indus Delta, Pakistan - Sher Shah Hassan; Muhammad Ajmal; Muhammad Arif Goheer; Zainab Ali; Muhammad Suleman (Theoretical and Applied Climatology, 2025)

A comparative study of fully automatic and semi-automatic methods for oil spill detection using Sentinel-1 data - Muhammad Iqbal Habibie; Hariyanto; Robby Arifandri; Zulfa Qonita; Pronika Kricella; Muh Hisyam Khoirudin; Noor Muhammad Ridha Fuadi; Nurul Shabrina; Nanda Itohasi Gutami; Siti Sadiah; Dewi Kartikasari; Muh.Mulyadi Agus Widodo; et al. (Environmental Monitoring and Assessment, 2025)

Quantum Chemical Insights into Metal-Ion Enhanced NLO Response of a Fluorescent Probe for Advanced Sensing Application - Asad Ullah; Muhammad Arif Ali; Sabir Ali Siddique; Muhammad Ibrahim; Hong Liang Xu; Abdul Rauf; Amal M. Al-Mohaimeed; Wedad A. Al-onazi; Muhammad Arshad (Journal of Fluorescence, 2025)

Synthesis and optimization of fluoxetine-loaded polymeric nanoparticles for dual therapeutic applications in cancer and depression - Muhammad Shoaib; Hira Arif; Asia Naz Awan; Moona Mehboob Khan; Sehrish Batool; Shakil Ahmed (DARU Journal of Pharmaceutical Sciences, 2025)

Nutritional value and therapeutic applications of Chenopodium album for human and livestock health: A comprehensive review - Mohamed E. Abd El-Hack; Ahmed A. Allam; Ahmed K. Aldhalmi; Mahmoud Kamal; Muhammad Arif; Abdullah S. Alawam; Hassan A. Rudayni; Ayman E. Taha; Elwy A. Ashour; Mohammad M.H. Khan (Food Bioscience, 2025)

A Comprehensive Review on Chemical Composition and Pharmacological Properties of Rosa damascena Mill. - Arshia Shahid; Mohd. Vaseem; Md. Arshad; Mohammad Khushtar; Mohd. Afroz Ahmad; Mohd. Ajmal; Saurabh Kumar Chauhan; Abubakar; Muhammad Arif (Current Pharmacology Reports, 2025)

CO2 capture using mixed amines: experimental DFT investigation with focus on improvements in cyclic efficiency and NO interference - Muhammad Haris; Arif Aziz; Muhammad Sohail; Waseem Sardar (Environmental Science and Pollution Research, 2025)

Hydrothermal integrated chemical treatment of microplastics for efficient degradation: Mechanistic insight and degradation behavior - Muhammad Zeeshan Gulzar; Guijian Liu; Balal Yousaf; Muhammad Imran; Muhammad Arif; Muhammad Nauman; Muhammad Irtaza Sajjad Haider; Bisma Sattar; Rabia Safeer; Samra Ijaz; Ruijia Liu (Journal of Water Process Engineering, 2025)

Influence of organic matter carbonization on pore structure and CO2/CH4 adsorption in marine kerogen: Insights from experimental observations and molecular simulation - Zhikai Liang; Zhenxue Jiang; Zhuo Li; Zixin Xue; Ruihua Chen; Muhammad Arif (Fuel, 2025)

The dynamics of bacterial communities during leaf decomposition of various species combinations in riparian forest buffers in China - Zhangting Chen; Muhammad Arif (Forest Ecology and Management, 2025)

Identification of multiple foodborne pathogens using single-atom nanozyme colorimetric sensor arrays and machine learning - Ying Li; Feng Chen; Yiping Liu; Muhammad Arif Khan; Hongbin Zhao; Hongmei Cao; Daixin Ye (Chemical Engineering Journal, 2025)

Interactive effects of soil moisture and temperature on chromium-induced microbial and enzymatic stress - Idrees Haider; Muhammad Arif Ali; Muhammad Sanaullah; Muhammad Taimoor Shakeel; Syed Atif Hasan Naqvi; Muhammad Akmal; Muhammad Abid Ali Khan; Muhammad Umer Iqbal; Niaz Ahmad; Mahmoud Moustafa; Mohammed O. Alshaharni; Uthman Algopishi (World Journal of Microbiology and Biotechnology, 2025)

Multiscale drought assessment with analyzing agricultural, meteorological, and hydrological impacts multi-index approaches (1991–2021) - Mingwu Zhou; Muhammad Haseeb; Zainab Tahir; Syed Amer Mahmood; Hania Arif; M. Abdullah-Al-Wadud; Aqil Tariq (Theoretical and Applied Climatology, 2025)

Global and tissue-specific transcriptomic dysregulation in human aging: Pathways and predictive biomarkers - Muhammad Arif; Andrea Lehoczki; György Haskó; Falk W. Lohoff; Zoltan Ungvari; Pal Pacher (GeroScience, 2025)
Aging is a universal biological process that impacts all tissues, leading to functional decline and increased susceptibility to age-related diseases, particularly cardiometabolic disorders. While aging is characterized by hallmarks such as mitochondrial dysfunction, chronic inflammation, and dysregulated metabolism, the molecular mechanisms driving these processes remain incompletely understood, particularly in a tissue-specific context. To address this gap, we conducted a comprehensive transcriptomic analysis across 40 human tissues using data from the Genotype-Tissue Expression (GTEx) project, comparing individuals younger than 40 years with those older than 65 years. We identified over 17,000 differentially expressed genes (DEGs) across tissues, with distinct patterns of up- and down-regulation. Enrichment analyses revealed that up-regulated DEGs were associated with inflammation, immune responses, and apoptosis, while down-regulated DEGs were linked to mitochondrial function, oxidative phosphorylation, and metabolic processes. Using gene co-expression network (GCN) analyses, we identified 1,099 genes as dysregulated nodes (DNs) shared across tissues, reflecting global aging-associated transcriptional shifts. Integrating machine learning approaches, we pinpointed key aging biomarkers, including GDF15 and EDA2R, which demonstrated strong predictive power for aging and were particularly relevant in cardiometabolic tissues such as the heart, liver, skeletal muscle, and adipose tissue. These genes were also validated in plasma proteomics studies and exhibited significant correlations with clinical cardiometabolic health indicators. This study provides a multi-tissue, integrative perspective on aging, uncovering both systemic and tissue-specific molecular signatures. Our findings advance understanding of the molecular underpinnings of aging and identify novel biomarkers that may serve as therapeutic targets for promoting healthy aging and mitigating age-related diseases.

KPT-330, A New Candidate Drug for Targeting NOTCH1 Overexpression in T-cell Acute Lymphoblastic Leukemia, An In Vitro and Silico Study - Fariha Naz; Saima Ejaz; Tayyaba Wali; Atiqa Nudrat; Mian Abdur Rehaman Arif; Muhammad Qandeel Waheed; Fatma Hussain; Saadiya Zia (Cell Biochemistry and Biophysics, 2025)

Biocompatible Nitro Group-Based Photosensitizer for AIE, Hypoxia, and Photodynamic Therapy. Experimental and Theoretical Approach - Maryam Rana; Munaza Pervaiz; Muhammad Arif Ali; Muhammad Ahmad; Laiqi Zhang; Shengnan Yin; Tansir Ahamad; Mansoor Akhtar (Journal of Fluorescence, 2025)

Safeguarding tourism economies: Managing the financial and ecological challenges of oil spills on coastal destinations - Arif Jameel; Muhammad Imran; Nawal Abdullah Adam; Sanjar Mirzaliev; Marguba Khidirov; Gao Yingying (Marine Pollution Bulletin, 2025)

Exploring omics solutions to reduce micro/nanoplastic toxicity in plants: A comprehensive overview - Samia Muhammad Arif; Ilham Khan; Muhammad Saeed; Sunbal Khalil Chaudhari; Mansour Ghorbanpour; Murtaza Hasan; Ghazala Mustafa (Science of The Total Environment, 2025)

The intersection of digital transformation and environmental responsibility in traditional manufacturing enterprises amid new productive forces - Meng Lin; Zhang Zhonghe; Muhammad Arif (Journal of Cleaner Production, 2025)

Boosted proton conduction in LAO electrolyte through Li segregation for High-Performance ceramic fuel cells - Nabeela Akbar; Muhammad Yousaf; M.A.K. Yousaf Shah; Jahangeer Ahmed; Asma Noor; Quazi Arif Islam; Yan Wu; Saad M. Alshehri; Naveed Mushtaq; Bin Zhu; Sara Paydar (Fuel, 2025)

Experimental investigation of slagging and fouling in co-combustion of bituminous coal and sorghum waste: Insights into ash morphology and mineralogy - Moch. Zulfikar Eka Prayoga; Nesha Adelia; Adi Prismantoko; Romelan Romelan; Fairuz Milkiy Kuswa; Maharani Dewi Solikhah; Arif Darmawan; Zainal Arifin; Bambang Teguh Prasetyo; Muhammad Aziz; Prabowo Prabowo; Hariana Hariana (Fuel, 2025)

Layer-by-layer concurrent encapsulation of probiotics and bioactive compounds with supplementation in intermediary layers: An establishing instrument for microbiome recharge, core safety, and targeted delivery - Muhammad Safiullah Virk; Muhammad Abdulrehman Virk; Mehak Gul; Muhammad Awais; Qiufang Liang; Tabussam Tufail; Mingming Zhong; Yufan Sun; Abdul Qayum; Ekram Abd El-Salam; John-Nelson Ekumah; Abdur Rehman; et al. (Food Hydrocolloids, 2025)

ENSO teleconnections and predictability of the boreal summer temperature over the Arabian Peninsula in C3S and Saudi-KAU seasonal forecast systems - Mansour Almazroui; M. Salman Khalid; Muhammad Adnan Abid; Irfan Ur Rashid; Shahzad Kamil; Haroon Siddiqui; M. Nazrul Islam; Muhammad Ismail; Muhammad Azhar Ehsan; Enda O'Brien; Mazen Asiri; Rayees Ahmed; et al. (Atmospheric Research, 2025)

Enhancing wheat resilience: biotechnological advances in combating heat stress and environmental challenges - Muhammad Arif; Muhammad Haroon; Ayesha Fazal Nawaz; Hina Abbas; Ruhong Xu; Luhua Li (Plant Molecular Biology, 2025)

A novel CLRN2 variant: expanding the mutation spectrum and its critical role in isolated hearing impairment - Farooq Ahmad; Arif Mahmood; Ibrahim Abdullah Almazni; Afnan Mohammed Shakoori; Fatemah Alhakami; Qamre Alam; Muhammad Ismail; Muhammad Umair (Genes & Genomics, 2025)

Immunological assessment of NSFu1: A novel fusion molecule constructed from structural proteins of SARS-CoV-2 for improving COVID-19 antibody detection - Shaista Arif; Mohsina Akhter; Aqsa Anwar; Sania Javaid; Zara Ashi; Mohsin Shad; Asad Rahman; Huda Abbas; Fouzia Ashraf; M. Waheed Akhtar; Muhammad Sajjad (Archives of Microbiology, 2025)

Unveiling the microplastics degradation and its transformative effects on soil nutrient dynamics and plant health – A systematic review - Abdul Rehman; Shan Zhong; Daolin Du; Xiaojun Zheng; Muhammad Saleem Arif; Samra Ijaz; Muhammad Raza Farooq (Sustainable Production and Consumption, 2025)

Dynamics of defense-related genes expression in shallot after UV-B-induced resistance against Fusarium acutatum showed time difference - Belinda Winona; Widhi Dyah Sawitri; Muhammad Idris; Valentina D.S. Handayani; Arif Wibowo; Deden D. Matra; Febri Doni; Ani Widiastuti (Physiological and Molecular Plant Pathology, 2025)

ICT-driven urbanization and energy security risk: Empirical evidence from Group 7 and Emerging 7 economies - Ahmed Usman; Syed Muhammad Muddassir Abbas Naqvi; Ilhan Ozturk; Ali Hassan; Asma Arif (Environmental Impact Assessment Review, 2025)

Phytoremediation Capacity of Saltwort (Salsola imbricata Forssk.) Determined by Tissue Organization and Physio-biochemical traits under Arid Saline Environments - Ummar Iqbal; Muhammad Sharjeel Arif; Muhammad Sharif; Abdul Wahab; Mehboob Ahmad; Muhammad Yousuf; Sadaf Rafiq; Sana Abid (Water, Air, & Soil Pollution, 2025)

Geospatial assessment of climate variability and drought patterns: a case study from Pakistan - Sher Shah Hassan; Muhammad Arif Goheer; Humera Farah; Faiza Hafeez; Khurram Sheraz; Javaria Fahad; Aqil Tariq (Theoretical and Applied Climatology, 2025)

Status and prospects of omics in lentil: understanding mechanisms and impact on stress breeding under changing climate - Fawad Ali; Yiren Zhao; Arif Ali; Mian Abdur Rehman Arif; Obaid Ullah Shah; Muhammad Atif Azeem; Li Liao; Zhiyong Wang (Journal of Plant Biochemistry and Biotechnology, 2025)

Optimized photocatalytic degradation of 2-naphthol using ZnO/rGO nanocomposites synthesized from palm kernel shell waste - Nuhaa Faaizatunnisa; Ratna Ediati; Enis Nadia M.D. Yusof; Arif Fadlan; Karelius Karelius; Ummu Kulsum; Muhammad Naufal Ariesta (Journal of Water Process Engineering, 2025)

Evolutionary analysis of ecological-production-living space-carrying capacity in tourism-centric traditional villages in Guangxi, China - Shanlin Wang; Yang Liping; Muhammad Arif (Journal of Environmental Management, 2025)

Pore network modelling of CO2-shale interaction for carbon storage: Swelling effect and fracture permeability - Amin Taghavinejad; Arash Rabbani; Gioia Falcone; Junlong Shang; Muhammad Arif; Yihuai Zhang (International Journal of Greenhouse Gas Control, 2025)

Enhanced photocatalytic overall water splitting via non-precious Zn-induced spatial separation of photoexcited excitons in polymeric carbon nitride - Zhengyuan Jin; Yangsen Xu; Bin Xue; Luhong Zhang; Xinzhong Wang; Nayab Arif; Muhammad Ahsan Iqbal; Lu Qi; Yu-Jia Zeng; Teruhisa Ohno (Fuel, 2025)

Predicting absolute adsorption of CO2 on Jurassic shale using machine learning - Changhui Zeng; Shams Kalam; Haiyang Zhang; Lei Wang; Yi Luo; Haizhu Wang; Zongjie Mu; Muhammad Arif (Fuel, 2025)

Smartphone-integrated inkjet-printed paper sensor and UV/Vis spectrophotometric method for on-site detection of As3+ and L-cysteine in food samples using novel AMTPP-functionalized silver nanoparticles - Sufian Rasheed; Kashif Hussain; Shan Arif; Abdul Rehman Umar; Syeda Bushra Anwar; Haji Muhammad; Kousar Yasmeen; Mustafa Tuzen; Muhammad Raza Shah (Food Chemistry, 2025)

Green synthesized silicon dioxide nanoparticles (SiO2NPs) ameliorated the cadmium toxicity in melon by regulating antioxidant enzymes activity and stress-related genes expression - Muhammad Sanaullah Malik; Asad Rehman; Iftikhar Hussain Shah; Samiah Arif; Kai Nan; Yumeng Yan; Shiren Song; Muhammad Khalid Hameed; Muhammad Azam; Yidong Zhang (Environmental Pollution, 2025)

A review on the preparation of carboxymethylcellulose-based membrane as polymer electrolyte for energy devices - Muhammad Bagus Arif; Sun Theo Constan Lotebulo Ndruru; Muhammad Ghozali (Biomass and Bioenergy, 2025)

Combined effect of abamectin and imidacloprid against three insects of cotton - Anam Ejaz; Ahmad Nawaz; Nazia Ehsan; Muhammad Jalal Arif (Journal of Plant Diseases and Protection, 2025)

Phenotypic and Molecular Screening for Yellow Rust Resistance in Chinese Wheat Hybrids as Impacted by Selection - Zainab Iftikhar; Muhammad Arif; Aamir Iqbal; Iqbal Munir; Sheng Quan Zhang; Chang Ping Zhao; Sajid Ali (Journal of Crop Health, 2025)
Exploring the potential of novel sources of wheat material is immensely important to combat the ever-changing pathogen causing wheat rust disease, associated with huge losses worldwide. This study focused on assessing rust (YR) resistance in Chinese wheat hybrids, combining molecular markers and field testing over two years with estimation of the impact of selection. Out of 416 hybrids, 108 were selected based on disease scoring parameters, showing negative genetic advancement for rust severity and coefficient of infection. The maximum rust severity reached 100% for four hybrids during the year 2017–18 whereas 70% for three hybrids during the year 2018–19. The maximum coefficient of infection was observed for four hybrids which were 100% (2017–18), whereas 70% for three hybrids (2018–19). Molecular genotyping with a set of five yellow rust resistance genes linked markers revealed that the most frequent molecular markers was Yr18 / Lr34 (among the YR markers), present in 92 out of 108 hybrids. All the five Yr genes were present only in 18 hybrids. Yr18 was the most common resistance gene detected in 85% hybrids, while Yr17 was the least detected gene (57%). Notably, the average coefficient of infection (ACI) was not directly associated with the number of resistant genes. Considering the overall performance, the hybrid lines 17BH002, 17BH057, 17BH073, 17BH109, 17BH123, 17BH128, 17BH190, 18BH026 and 17BH155 had an overall low yellow rust severity and co-efficient of infection and could be considering promising lines for further utilization. Clustering based on rust resistance genes categorized hybrids into five main clusters for YR resistance genes, showing variability among these valuable genetic resources. The observed variability in this study can be utilized for future breeding programs focused on developing resistant wheat varieties.

Cross-climatic comparison of microbial stress-responsive genes in urban parks: A comparative analysis - Saeed ur Rahman; Xinxin Liu; Muhammad Khalid; Asad Rehman; Junfeng Cao; Chang Zhao; Haoxin Tan; Samiah Arif; Bangxiao Zheng; Yucheng Bian; Ari Jumpponen; D. Johan Kotze; et al. (Urban Forestry & Urban Greening, 2025)

Valproic acid-induced oxidative stress: Systematic review, meta-analysis and network pharmacology highlights disruption in antioxidant pathways in rodents - Muhammad Arif Asghar; Shixin Tang; Bing Wan; Ying Chen; Xiao Zhang; Qinjian Zhao (Toxicology and Applied Pharmacology, 2025)

Progress in hybrid and electric propulsion technologies for fishing vessels: An extensive review and prospects - Samsul Ma'arif; Muhammad Arif Budiyanto; Sunaryo; Gerasimos Theotokatos (Ocean Engineering, 2025)

Tectono-magmatic evolution of the Indian crust in western Himalayas during Paleoproterozoic: Insights from Nanga Parbat and Indus syntaxis in northern Pakistan - Muhammad Sajid; Michael Wiedenbeck; Muhammad Arif; Johannes Glodny; Nowrad Ali; Humaad Ghani; Jessica A. Stammeier (Gondwana Research, 2025)

Transcriptome-wide identification of microRNAs regulating plant immunity in Gossypium arboreum L. - Abdul Manan Khan; Muhammad Abu Bakar Saddique; Sajid Fiaz; Saba Zafar; Kotb A. Attia; Yaser M. Hafez; Arif Ahmed Mohammed (Genetic Resources and Crop Evolution, 2025)

Smartphone-assisted colorimetric sensor arrays based on nanozymes for high throughput identification of heavy metal ions in salmon - Shuo Wu; Muhammad Arif Khan; Tianzeng Huang; Xing Liu; Rui Kang; Hongbin Zhao; Hongmei Cao; Daixin Ye (Journal of Hazardous Materials, 2024)

Encapsulation, optimization, and characterization of lycopene using soy protein isolate-peach gum conjugate as wall material - Arif Hussain; Muhammad Hussain; Waqas Ashraf; Khubaib Ali; Abid Hussain; Hsu Mon Phyo; Muhammad Umair Khalid; Mudassar Hussain; Zhang Lianfu (Food Bioscience, 2024)

Preparation, characterization, and antifungal capacity of Co-encapsulated anisaldehyde and cinnamaldehyde within pullulan-stabilized nanoemulsions for bread preservation - Muhammad Umair Khalid; Hsu Mon Phyo; Farazia Hassan; Anam Mushtaq; Arif Hussain; Mudassar Hussain; Tawfiq Alsulami; Weirong Yao (Food Bioscience, 2024)

Overexpression of Gossypium arboreum 3-ketoacyl-CoA synthase 6 (GaKCS6) gene enhanced leaf epicuticle wax in Gossypium hirsutum L. and improved tolerance against whitefly - Muhammad Umair Majid; Rabiah Ashraf; Basit Jabbar; Usman Arif; Fatima Batool; Sameera Hassan; Bushra Rashid (Biocatalysis and Agricultural Biotechnology, 2024)

RETRACTED ARTICLE: Bio-Graphene Foam: A Robust Solution for Adsorptive and Sustainable Chlorophenol Removal from Wastewater - Sidra; Muhammad Hamid khan; Wang Jin Quan; Shakeel Ahmad; Jingling Ji; Xinhua Xiao; Haseen Ullah; Arif Nawaz; Farman Ali; Nisar Ali (Water, Air, & Soil Pollution, 2024)

An SNP based genotyping assay for genes associated with drought tolerance in bread wheat - Abdul Rauf; Muhammad Ali Sher; Umar Farooq; Awais Rasheed; Muhammad Sajjad; Ruilian Jing; Zulqurnain Khan; KOTB A. Attia; Arif Ahmed Mohammed; Sajid Fiaz; Jing Chen; Shoaib Ur Rehman (Molecular Biology Reports, 2024)

Cross-species substitution matrix comparison of Tomato leaf curl New Delhi virus (ToLCNDV) with medicinal plant isolates - Muhammad Arif (Journal of Plant Diseases and Protection, 2024)
The main objective of this study was to estimate and compare substitution matrixes of nucleotide frequencies for Tomato leaf curl New Delhi virus (ToLCNDV) with recently identified begomoviral isolates from two medicinal false daisy ( Eclipta prostrata ) and tomato ( Solanum lycopersicum ) plants. The ToLCNDV has become a significant limitation to vegetables production in many countries. A polymerase chain reaction was conducted to conserve the existence of begomoviral infection. The acquired amplicon was amplified using primers appropriate to the sequence in order to retrieve the full genome. The sequence analysis has confirmed the presence of ToLCNDV in symptomatic plants. The complete genome sequence having a 2.6–2.7 kb entire genome of ToLCNDV was obtained. An investigation of the phylogenetic and evolutionary history has verified the connection between this virus and other closely related viruses. The available nucleotide frequencies of codon regions ( A , T / U , C , G ) with newly isolates revealed 20–28% substitution matrixes. There was a minimal difference of nucleotide frequencies’ with already submitted database of this virus. Substitution matrixes, which quantify the probability of nucleotide substitutions evolving over a period of time, offer valuable information about mutation patterns and the forces driving evolution. This comparative analysis enhanced the comprehension of the genetic diversity of ToLCNDV and its possible consequences on medicinal plants. It also assisted in the formulation of efficient control measures and the preservation of begomoviruses in medicinal plant biodiversity. The information presented here is highly valuable for understanding the ToLCNDV biology and epidemiology, and it would also assist in disease management in the future.

Cap-snatching mechanism-mediated unveiling of the transcriptional initiation sites of two distinct begomoviruses - Muhammad Arif (Journal of Plant Diseases and Protection, 2024)
Significant economic losses are inflicted by plant viruses, which pose a risk to sustainable agriculture. The proliferation of novel viral diseases is predominantly attributable to factors such as climate change, international trade, and the rapid evolutionary capabilities of viruses. Begomoviruses are a major group of plant-infecting viruses that pose an imminent threat to global agriculture by causing devastating viral diseases in many crop species. The transcriptional start sites (TSSs) of many plant viruses are typically found in the intergenic region (IR), which is the non-coding (NC) area between the viral genes. The promoters play a crucial role in initiating the transcription process by aiding in the recruitment of cellular transcription machinery. The TSSs are precise nucleotide sequences where RNA polymerase initiates the transcription process. The primary objective of this study was to determine the total number of TSSs for two devastating begomoviruses, family: Geminiviridae, Cotton leaf curl Multan virus (CLCuMuV) and Ageratum yellow vein mosaic virus (AYVMV), using the cap-snatching method in conjunction with one heterologous plant virus. These two begomoviruses, along with their infectious clones, were intentionally infected with selected heterologous plant virus in N. benthamiana plants. The identification of the 5′ ends of heterologous viral mRNA was accomplished by employing high-throughput sequencing to assess the capped RNA leaders (CRLs). The determination of the 5′ termini of suspected begomoviral mRNAs was achieved by aligning the collected CRLs of heterologous virus with the genome of each begomovirus, taking into account only those that were a perfect match with the begomoviral genome. In this study, the TSSs of both begomoviruses were identified via complementary approach. The utilization of high-throughput sequencing for both begomoviruses has facilitated the acquisition of millions of sequences. Comprehending the TSSs and promoter components of begomoviruses is crucial for understanding their ability to cause disease, their interactions with host organisms, and for developing effective methods to manage and control the diseases, they inflict on economically significant crop plants.

Genetic diversity analysis of pea (Pisum sativum l.) landraces by utilizing simple sequence repeat markers - Uzma Arif; Summaira Ali; Badr Alharthi; Muhammad Farhan Khan Pasha; Hafiz Muhammad Ahmad; Muhammad Jamil Ahmed; Ayaz Ahmed Arif (Genetic Resources and Crop Evolution, 2024)

Tsunami hazard assessment for the Cilegon industrial zone, Java, Indonesia, by considering various digital elevation model (DEM) datasets and fault source models - Sesar Prabu Dwi Sriyanto; Arif Nurokhim; Teguh Sulistian; Indra Gunawan; Rizki Iman Sari; Brilian Tatag Samapta; Iman Fatchurochman; Fajar Triady Mugiarto; Rifqi Muhammad Harrys (Arabian Journal of Geosciences, 2024)

Carotenoid cellular uptake and antioxidant activity from differently cooked semolina and whole wheat pasta - Hannah Oduro-Obeng; Muhammad Mudassir Arif Chaudhry; Daniel Zogona; Jitendra Paliwal; Bin Xiao Fu; Trust Beta (Journal of Cereal Science, 2024)

Mechanical properties of shale during pyrolysis: Atomic force microscopy and nano-indentation study - Zhikai Liang; Zhenxue Jiang; Xianglu Tang; Ruihua Chen; Muhammad Arif (International Journal of Rock Mechanics and Mining Sciences, 2024)

Bio-based plastics, biodegradable plastics, and compostable plastics: biodegradation mechanism, biodegradability standards and environmental stratagem - Sabzoi Nizamuddin; Abdul Jabbar Baloch; Chengrong Chen; Muhammad Arif; Nabisab Mujawar Mubarak (International Biodeterioration & Biodegradation, 2024)

Preparation and functional characterization of pullulan-sodium alginate composite film enhanced with ultrasound-assisted clove essential oil Nanoemulsions for effective preservation of cherries and mushrooms - Arif Rashid; Abdul Qayum; Syed Asim Shah Bacha; Qiufang Liang; Yuxuan Liu; Lixin Kang; Zhuzhong Chi; Runhao Chi; Xu Han; John-Nelson Ekumah; Muhammad Safi Ullah Virk; Xiaofeng Ren; et al. (Food Chemistry, 2024)

Novel pullulan-sodium alginate film incorporated with anthocyanin-loaded casein-carboxy methyl cellulose nanocomplex for real-time fish and shrimp freshness monitoring - Arif Rashid; Abdul Qayum; Syed Asim Shah Bacha; Qiufang Liang; Yuxuan Liu; Lixin Kang; Zhuzhong Chi; Runhao Chi; Xu Han; John-Nelson Ekumah; Muhammad Safiullah Virk; Xiaofeng Ren; et al. (Food Hydrocolloids, 2024)

Integrated assessment of groundwater quality dynamics and Land use/land cover changes in rapidly urbanizing semi-arid region - Arif ullah; Sajjad Hussain; Yicheng Wang; Muhammad Awais; Meer Muhammad Sajjad; Nuaman Ejaz; Umar Javed; Muhammad Waqas; Xiao Zhe; Javed Iqbal (Environmental Research, 2024)

Turning trash into Treasure: Extracting precious metals from e-waste with Electrochemically Exfoliated graphene derivatives - Mamoona Hayat; Muhammad Waseem; Saira Arif; Junaid Ali; Abdul Sattar; Sobia Dilpazir; Khadim Hussain; Lubna Tabassam (Chemical Engineering Journal, 2024)

Influence of probiotic strains on growth performance, carcass characteristics and seasonal changes of growing New Zealand white rabbits - Elwy A. Ashour; Islam M. Youssef; Ahmed I. Elsherbeni; Muhammad Arif; Guillermo Tellez-Isaias; Ahmed K. Aldhalmi; Ayman A. Swelum; Mohamed E. Abd El-Hack (Tropical Animal Health and Production, 2024)

Tailoring tea residue-derived nitrogen-doped activated carbon for CO2 adsorption: influence of activation temperature and activating agents - Amirul Hafiiz Ruhaimi; Muhammad Arif Ab Aziz (Environmental Science and Pollution Research, 2024)

Evaluation of carob tree (Ceratonia siliqua L.) pods, through three different drying techniques, and ultrasonic assisted extraction, for presence of bioactives - Ashiq Hussain; Muhammad Rehan Arif; Adnan Ahmed; Salah Laaraj; Nida Firdous; Muhammad Qasim Ali; Haya Fatima; Shazia Yaqub; Samina Kauser; Rizwan Nisar; Faiza Iftikhar Gorsi; Ghulam Mueen Ud Din; et al. (South African Journal of Botany, 2024)

Depositional architecture of early rift non-marine systems and implications for reservoir development: Oligocene to Miocene Al Wajh Formation, Midyan Basin of Red Sea, Saudi Arabia - Muhammad Naveed Butt; Arif Hussain; Muhammad Hammad Malik; Abduljamiu O. Amao; Ardiansyah Koeshidayatullah; Cornel Olariu; Abdulwahab Muhammad Bello; Khalid Al-Ramadan (Marine and Petroleum Geology, 2024)

Carbon-based nanomaterials (CNMs) modified TiO2 nanotubes (TNTs) photo-driven catalysts for sustainable energy and environmental applications: A comprehensive review - Md. Arif Hossen; Riyadh Ramadhan Ikreedeegh; Azrina Abd Aziz; Abdelmoumin Yahia Zerga; Muhammad Tahir (Journal of Environmental Chemical Engineering, 2024)

Self-templated formation of ZnNC microtube with high oxygen reduction reaction overpotential for Zn-based catalyst - Ayaz Mahsud; Muhammad Arif; Asif Mehmood; Mohammad Azam; Xiaobing Wang; Zongxian Yang; Zhansheng Lu (Journal of Environmental Chemical Engineering, 2024)

Design, synthesis, and electronic structure modulation of ORR electrocatalysts - Muhammad Arif; Ayaz Mahsud; Tahir Muhmood; Francis Leonard Deepak (Journal of Environmental Chemical Engineering, 2024)

Comparative analysis of machine learning models for predicting PM2.5 concentrations using meteorological and chemical indicators - Muhammad Haseeb; Zainab Tahir; Syed Amer Mahmood; Hania Arif; Khalid F. Almutairi; Walid Soufan; Aqil Tariq (Journal of Atmospheric and Solar-Terrestrial Physics, 2024)

Exploring the interface dynamics of emulsion gel via a novel non-destructive technique provides insights into the underlying mechanism of gel formation, water mobility, functionality and structural variations - Abdul Qayum; Arif Rashid; Asif Ali Khan; Mingming Zhong; Yuxuan Liu; Muhammad Hussain; Muhammad Safiullah Virk; Zahoor Ahmed; Abdur Rehman; Abid Hussain; Qiufang Liang; Xiaofeng Ren; et al. (Food Bioscience, 2024)

Reply to Discussion: “Haiyang Zhang and Muhammad Arif. Residual trapping capacity of subsurface systems for geological storage of CO2: Measurement techniques, meta-analysis of influencing factors, and future outlook. Earth-Science Reviews (2024): 104764.” - Haiyang Zhang; Muhammad Arif (Earth-Science Reviews, 2024)

Fine-tuning plant valuable secondary metabolite biosynthesis via small RNA manipulation: strategies and potential - Nur Irdina Izzatie Mohd Zahid; Syed Muhammad Iqbal Syed Othman; Arif Faisal Mustaffa; Ismanizan Ismail; Muhamad Hafiz Che-Othman (Planta, 2024)

Smoothed particle hydrodynamics simulation of debris flow on deposition area - Muhammad Khairi A. Wahab; Mohd Remy Rozainy Mohd Arif Zainol; Jazaul Ikhsan; Mohd Hafiz Zawawi; Mohamad Aizat Abas; Norazian Mohamed Noor; Norizham Abdul Razak; Neeraj Bhardwaj; Siti Multazimah Mohamad Faudzi (Natural Hazards, 2024)

Exploring vortex dynamic efficiency in hydro-suction system: a combined experimental and numerical investigation - Mohammed Hamid Rasool; Mohd Remy Rozainy Mohd Arif Zainol; Norizham Abdul Razak; Muhammad Khairi A. Wahab; Neeraj Bhardwaj (Modeling Earth Systems and Environment, 2024)

A holistic overview of the in-situ and ex-situ carbon mineralization: Methods, mechanisms, and technical challenges - Farzain Ud Din Kirmani; Arshad Raza; Sheraz Ahmad; Muhammad Arif; Mohamed Mahmoud (Science of The Total Environment, 2024)

Can urea-coated fertilizers be an effective means of reducing greenhouse gas emissions and improving crop productivity? - Muhammad Umair Hassan; Huang Guoqin; Muhammad Saleem Arif; Muhammad Salman Mubarik; Haiying Tang; Huifang Xu; Binjuan Yang; Quan Zhou; Awais Shakoor (Journal of Environmental Management, 2024)

Quality and microstructural analysis of chickpea-enriched wheat semolina pasta using X-ray micro-computed tomography - Obasi Ukpai Ukoji; Muhammad Mudassir Arif Chaudhry; Lindsey Boyd; Elaine Sopiwnyk; Jitendra Paliwal (Journal of Cereal Science, 2024)

CO2-brine interactions in anhydrite-rich rock: Implications for carbon mineralization and geo-storage - Abubakar Isah; Mohamed Mahmoud; Arshad Raza; Mobeen Murtaza; Muhammad Arif; Muhammad Shahzad Kamal (International Journal of Greenhouse Gas Control, 2024)

Effect of formation brine on interfacial interaction: Implications for CO2 storage - Johny Mouallem; Muhammad Arif; Abubakar Isah; Arshad Raza; Md Motiur Rahman; Mohamed Mahmoud; Muhammad Shahzad Kamal (Fuel, 2024)

Preparation, characterization and functional evaluation of soy protein isolate-peach gum conjugates prepared by wet heating Maillard reaction - Arif Hussain; Muhammad Hussain; Waqas Ashraf; Aiman Karim; Sahibzada Muhammad Aqeel; Adil Khan; Asif Hussain; Salman Khan; Zhang Lianfu (Food Research International, 2024)

Synergistic interactions and reaction mechanisms of biochar surface functionalities in antibiotics removal from industrial wastewater - Muhammad Irtaza Sajjad Haider; Guijian Liu; Balal Yousaf; Muhammad Arif; Kiran Aziz; Aniqa Ashraf; Rabia Safeer; Samra Ijaz; Krzysztof Pikon (Environmental Pollution, 2024)

Review on optimizing dairy sector efficiency: Integrating of genetic markers with managemental techniques - Muhammad Safdar; Muhammad Kaleem; Phelipe Magalhães Duarte; Sina Salajegheh Tazerji; Mehmet Ozaslan; Shahin Hassanpour; Jayadev Rath; Swagatika Priyadarsini; Muhammad Arif Rizwan (Ecological Genetics and Genomics, 2024)

Evaluation of Treatment Methods for Nitro-Aromatic Compounds from TNT Contaminated Soil in Pebbles Packed Reed-Beds Mesocosm - Mahwish Ali; Muhammad Arif; Shama Seher; Abdul Haleem; Syeda Mehpara Farhat; Syeda Fariha Hassan; Safia Ahmed (Water, Air, & Soil Pollution, 2024)

Molecular Characterization and Comparative Transcriptomic Analysis of Hr-Lcyb and Hr-Psy Genes for Carotenoids Synthesis in Sea Buckthorn (Hippophae rhamnoides L.) - Shazia Arif; Hafiz Muhammad Ahmed; Safira Attacha; Kotb A. Attia; Arif Ahmed Mohammed; Saira Ishaq; Shahid Iqbal Awan; Sajid Fiaz; Waseem Alam; Seung Hwan Yang (Journal of Soil Science and Plant Nutrition, 2024)

Skipping irrigation at pre- and post-anthesis stages influences grain yield and starch contents of bread wheat derived from synthetic or landraces - Sajid Shokat; Mian Abdur Rehman Arif; Muhammad Qandeel Waheed; Fulai Liu; Carlos Guzmán; Sukhwinder Singh (Cereal Research Communications, 2024)
This study aims to evaluate the role of genetic diversity originated from three-way crosses of landraces and synthetic bread wheat derivatives attempted with elite cultivars to identify the genotypes having better grain yield as well as better starch contents under flowering stage drought stress. In total, 50 genotypes comprised of 47 derivatives of landraces and synthetics, and three standard varieties were grown in the fields of CIMMYT, Obregon following alpha lattice design with two replications. Drought stress was imposed by stopping the irrigation before anthesis and post-anthesis stages. Different traits related to physiological adaptations, earliness, grain yield and starch contents were decreased under drought stress except amylose which increased significantly. Canopy temperature depression was not significantly affected by drought stress. Further, we identified strong correlation of grain yield with plant height, normalized difference in vegetation index, plant maturity, spike length, grain number and thousand grain weight but negative with canopy temperature depression. Non-significant correlation of amylose and amylopectin was recorded with grain yield. Results revealed that genetic diversity derived from landraces and synthetic bread wheat can improve grain yield and starch contents but simultaneous improvement of both is elusive.

Tailoring structural and optical properties of Cu(II)-induced MgAl2O4 nanoparticles and their response to toxic dyes under solar illumination - Muhammad Javed; Naeem Akbar; Ayaz Arif Khan; Asad Masood; Naeem Ahmed; Muhammad Junaid Khan; Nisar Ahmed; Said Nasir Khisro; Muhammed Ali Shaikh Abdul Hameed (Environmental Science and Pollution Research, 2024)

Modeling and monitoring cotton production using remote sensing techniques and machine learning: a case study of Punjab, Pakistan - Sher Shah Hasan; Muhammad Arif Goheer; Muhammad Uzair; Saba Fatima (Environment, Development and Sustainability, 2024)

Long-term raw crop residue but not burned residue incorporation improved soil multifunctionality in semi-arid agroecosystems - Aqeel Ahmad; Muhammad Saleem Arif; Sher Muhammad Shahzad; Tahira Yasmeen; Awais Shakoor; Shahid Iqbal; Asam Riaz; Anjum Zahid; Stephen James Chapman (Soil and Tillage Research, 2024)

Diagenetic variability in Tertiary, syn-rift mixed siliciclastic‑carbonate depositional system (Lower Musayr Formation), Red Sea, Saudi Arabia - Arif Hussain; Abdulwahab Bello; Muhammad Naveed Butt; Muhammad Hammad Malik; Ardiansyah Koeshidayatullah; Abduljamiu Amao; Cornel Olariu; Khalid Al-Ramadan (Sedimentary Geology, 2024)

Designing and synthesis of perovskite nanocrystals: a promising wide-spectrum solar light–responsive photocatalyst and lead ion sensor - Nisar Ali; Shakeel Ahmad; Arif Nawaz; Manzoor Khan; Aman Ullah; Muhammad Idrees; Adnan Khan; Wilayat Khan (Environmental Science and Pollution Research, 2024)

Ecological-economic assessment of forest land degradation neutrality in the Indus River Basin of Pakistan - Muhammad Arif; Hira Amin; Nowsherwan Zarif; Liu Xiangyue; Cao Yukun (Environment, Development and Sustainability, 2024)

Unveiling antibiotic contamination in surface water: A study of the Huaihe River Basin's Huaibei Plain, a significant Chinese herbal medicine planting region - Haixin Wu; Ruijia Liu; Guijian Liu; Miao He; Muhammad Arif; Fengming Li; Wen Si; Zhen Yue; Hao Hu (Science of The Total Environment, 2024)

Enhancing storage and gastroprotective viability of Lactiplantibacillus plantarum encapsulated by sodium caseinate-inulin-soy protein isolates composites carried within carboxymethyl cellulose hydrogel - Muhammad Safiullah Virk; Muhammad Abdulrehman Virk; Qiufang Liang; Yufan Sun; Mingming Zhong; Tabussam Tufail; Arif Rashid; Abdul Qayum; Abdur Rehman; John-Nelson Ekumah; Junxia Wang; Yongjun Zhao; et al. (Food Research International, 2024)

Corrigendum to “Could soil microplastic pollution exacerbate climate change? A meta-analysis of greenhouse gas emissions and global warming potential” [Environ. Res. 252 (2024) 118945/ ER-23-14694R1] - Shahid Iqbal; Jianchu Xu; Muhammad Saleem Arif; Awais Shakoor; Fiona R. Worthy; Heng Gui; Sehroon Khan; Dengpan Bu; Sadia Nadir; Sailesh Ranjitkar (Environmental Research, 2024)

Could soil microplastic pollution exacerbate climate change? A meta-analysis of greenhouse gas emissions and global warming potential - Shahid Iqbal; Jianchu Xu; Muhammad Saleem Arif; Awais Shakoor; Fiona R. Worthy; Heng Gui; Sehroon Khan; Dengpan Bu; Sadia Nader; Sailesh Ranjitkar (Environmental Research, 2024)

Identification of bacterial community in a rapid composting method using 16SrDNA genes sequencing - Muhammad Shahid; Waqar Ahmed; Abdul Basit Khan; Zafar Iqbal Shams; Afsheen Arif (Biodegradation, 2024)

Dam inundation reduces ecosystem multifunctionality following riparian afforestation in the Three Gorges Reservoir Region - Jie Zheng; Muhammad Arif; Lijuan Li; Xinrui He; Yuanyuan Wu; Wenqiu Cao; Peixuan Yan; Changxiao Li (Journal of Environmental Management, 2024)

Identification of provenance of Basmati rice grown in different regions of Punjab through multivariate analysis - Muhammad Saifullah; Awais Nisar; Ramzan Akhtar; Syed M. Husnain; Shamila Imtiaz; Bashir Ahmad; Munib Ahmed Shafique; Saira Butt; Muhammad Arif; Abid Majeed Satti; Muhammad Shahzad Ahmed; Simon D. Kelly; et al. (Food Chemistry, 2024)

Comprehensive experimental assessment of Samanea saman wood and leaves waste combustion in the aspect of ash-related problem - Suyatno Suyatno; Hafizh Ghazidin; Hanafi Prida Putra; Fairuz Milkiy Kuswa; Moch Zulfikar Eka Prayoga; Atok Setiyawan; Prabowo Prabowo; Kusmiyati Kusmiyati; Nina Konitat Supriatna; Arif Darmawan; Firman Bagja Juangsa; Muhammad Aziz; et al. (Bioresource Technology Reports, 2024)

Unveiling the chemical profile, synergistic antibacterial and hemolytic effects of Cymbopogon citratus and Tachyspermum ammi leaves - Shabbir Hussain; Amina Zahid; Muhammad Imran; Shazma Massey; Muhammad Riaz; Muhammad Sagir; Muhammad Shahid; Wissem Mnif; Shahid Iqbal; Munawar Iqbal; Arif Nazir (Biocatalysis and Agricultural Biotechnology, 2024)

A Computational Predictor for Accurate Identification of Tumor Homing Peptides by Integrating Sequential and Deep BiLSTM Features - Roha Arif; Sameera Kanwal; Saeed Ahmed; Muhammad Kabir (Interdisciplinary Sciences: Computational Life Sciences, 2024)

A control rod worth prediction using Adaptive Neuro-Fuzzy Inference System for Pre-Calibration Method at TRIGA PUSPATI Reactor - Teh Zhi Hui; Nur Syazwani Mohd Ali; Mohd Sabri Minhat; Jasman Zainal; Muhammad Arif Sazali; Muhammad Syahir Sarkawi; Khairulnadzmi Jamaluddin; Nor Afifah Basri; Mohsin Mohd Sies; Nahrul Khair Alang Md Rashid (Annals of Nuclear Energy, 2024)

Comparative Assessment of Bioactive Compounds, Fruit Quality Attributes and Sugar Profiling in Early Maturing Table Grape (Vitis Vinifera L.) Cultivars from Pothohar, Pakistan - Muhammad Tahir Akram; Rashad Qadri; Muhammad Azam Khan; Arif Atak; Mehwish Liaquat; Tanveer Hussain; Muhammad Mumtaz Khan; Muhammad Azam; Mahmood ul Hasan (Applied Fruit Science, 2024)

Bioactive compounds isolated from Solanum nigrum remarkably inhibit cancerous activity in cancer cell lines - Aisha Nawaz; Adil Jamal; Amina Arif; Shumaila Kiran; Muhammad Naveed Shahid; Shafia Arshad; Zeeshan Shamim (South African Journal of Botany, 2024)

Green synthesis of ZnO nanocubes from Ceropegia omissa H. Huber extract for photocatalytic degradation of bisphenol An under visible light to mitigate water pollution - Awais Ahmad; Muhammad Ramzan Khawar; Ikram Ahmad; Muhammad Hassan Javed; Anees Ahmad; Abdul Rauf; Umer Younas; Arif Nazir; Dongwhi Choi; Abdulnasser M. Karami (Environmental Research, 2024)

Residual trapping capacity of subsurface systems for geological storage of CO2: Measurement techniques, meta-analysis of influencing factors, and future outlook - Haiyang Zhang; Muhammad Arif (Earth-Science Reviews, 2024)

Effects of biodegradable- and non-biodegradable-rich waste separation on ash deposition behaviour during coal and refuse-derived fuel co-combustion - Adi Prismantoko; Feri Karuana; Ardi Nugroho; Puji Agus Santoso; Hanafi Prida Putra; Arif Darmawan; Muhammad Akhsin Muflikhun; Indro Pranoto; Muhammad Aziz; Hariana Hariana (Waste Management, 2024)

The development of plastic waste and sewage sludge co-pyrolyzed biochar composites with improved interfacial characteristics for the effective removal of ciprofloxacin - Aniqa Ashraf; Guijian Liu; Muhammad Arif; Balal Yousaf; Pervaiz Akhtar; Audil Rashid; Humaira Gulzaman; Rabia Safeer; Muhammad Saqib Rashid; Muhammad Irtaza Sajjad Haider (Process Safety and Environmental Protection, 2024)

Understanding the Irreversible Evolution of Coal Permeability Under Cyclic Axial Deviatoric Stress - Jiafeng Liu; Xiaomeng Xu; Yihuai Zhang; Ziheng Wang; Muhammad Arif; Qiang Wang (Natural Resources Research, 2024)

Toxicological assessment of dietary exposure of polyethylene microplastics on growth, nutrient digestibility, carcass and gut histology of Nile Tilapia (Oreochromis niloticus) fingerlings - Muhammad Mahmood; Syed Makhdoom Hussain; Pallab K. Sarker; Shafaqat Ali; Muhammad Saleem Arif; Nadia Nazish; Danish Riaz; Nisar Ahmad; Bilal Ahamad Paray; Adan Naeem (Ecotoxicology, 2024)

Microorganism-mediated biodegradation for effective management and/or removal of micro-plastics from the environment: a comprehensive review - Hassan Zahid; Nimra Afzal; Muhammad Maaz Arif; Mahnoor Zahid; Samia Nawab; Malik Muhammad Qasim; Farhat Naseem Alvi; Sumbal Nazir; Ishrat Perveen; Naaz Abbas; Yasar Saleem; Sania Mazhar; et al. (Archives of Microbiology, 2024)

Does no-till crop management mitigate gaseous emissions and reduce yield disparities: An empirical US-China evaluation - Awais Shakoor; Elise Pendall; Muhammad Saleem Arif; Taimoor Hassan Farooq; Shahid Iqbal; Sher Muhammad Shahzad (Science of The Total Environment, 2024)

Tracking the Feeding Mechanism of Sap-Sucking Insect-Pests Through Electropenetrography (EPG) - Usama Bin Tayyab; Muhammad Jalal Arif; Muhammad Dildar Gogi; Shamim Akhtar; Muhammad Jawad Abdullah; Faisal Ali (Journal of Insect Behavior, 2024)

Genome-wide screening and evolutionary analysis of ZIP (ZRT–IRT like proteins) family in cowpea (Vigna unguiculata L.) - Arif Ullah; Zamarud Shah; Iqbal Munir; Hamza Iqbal; Muhammad Zulfiqar Ahmad; Warda Sultan; Afrasyab Khan (Genetic Resources and Crop Evolution, 2024)

Underground hydrogen storage prospects in the Kingdom of Saudi Arabia - Arshad Raza; Mohamed Mahmoud; Muhammad Arif; Saad Alafnan (Fuel, 2024)

Multifunctional role of nanoparticles for the diagnosis and therapeutics of cardiovascular diseases - Ihtesham Arshad; Ayesha Kanwal; Imran Zafar; Ahsanullah Unar; Hanane Mouada; Iashia Tur Razia; Safina Arif; Muhammad Ahsan; Mohammad Amjad Kamal; Summya Rashid; Khalid Ali Khan; Rohit Sharma (Environmental Research, 2024)

Experimental study of confined masonry walls with lap splice reinforcement subjected to cyclic loads - Angga Arief; Siti Aisyah Nurjannah; Yoga Megantara; Muhammad Rusli; Ferri Eka Putra; Arif Noviyanto (Engineering Structures, 2024)

Root exudation and associated traits explain the differentiation of plant survival strategy in a drawdown zone in China - Xueting Yin; Songlin Zhang; Shanshan Chen; Muhammad Arif; Maohua Ma; Ping Huang; Qiao Chen; Shengjun Wu (Plant and Soil, 2024)

Efficacy of Green Synthesized Silver Based Nanomaterials Against Early Blight of Tomato Caused by Alternaria solani - Muhammad Usman; Muhammad Atiq; Nasir Ahmed Rajput; Shahbaz Talib Sahi; Mohsin Shad; Nian Lili; Shahid Iqbal; Asif Mahmood Arif; Usama Ahmad; Khurram Shehzad Khan; Muhammad Asif; Fasih Ullah Haider (Journal of Crop Health, 2024)

Ultrafiltration membrane fabricated from polyethylene terephthalate plastic waste for treating microalgal wastewater and reusing for microalgal cultivation - Hemamalini Rawindran; Nur Arif bin Hut; Dhita Karunia Vrasna; Pei Sean Goh; Jun Wei Lim; Chin Seng Liew; Chii-Dong Ho; Hooi-Siang Kang; Muhammad Kashif Shahid; Hui-Suan Ng; Mohamed A. Habila; Kuan Shiong Khoo (Chemosphere, 2024)

Fundamental opportunities and challenges of nutraceutical noodles enriched with agri-food by-products - Zahoor Ahmed; Jin Chen; Tabussam Tufail; Anam Latif; Muhammad Arif; Riaz Ullah; Ali S. Alqahtani; Bin Xu (Trends in Food Science & Technology, 2024)

Depositional and diagenetic controls on the reservoir quality of Early Miocene syn-rift deep-marine sandstones, NW Saudi Arabia - Muhammad Naveed Butt; Stephen G. Franks; Arif Hussain; Abduljamiu Olalekan Amao; Abdulwahab Muhammad Bello; Khalid Al-Ramadan (Journal of Asian Earth Sciences, 2024)

Cassia Angustifolia Primed ASCs Accelerate Burn Wound Healing by Modulation of Inflammatory Response - Saba Tasneem; Hafiz Ghufran; Maryam Azam; Amna Arif; Musab Bin Umair; Muhammad Amin Yousaf; Khurrum Shahzad; Azra Mehmood; Kausar Malik; Sheikh Riazuddin (Tissue Engineering and Regenerative Medicine, 2024)

Hydrogeochemistry and prediction of arsenic contamination in groundwater of Vehari, Pakistan: comparison of artificial neural network, random forest and logistic regression models - Javed Iqbal; Chunli Su; Maqsood Ahmad; Muhammad Yousuf Jat Baloch; Abdur Rashid; Zahid Ullah; Hasnain Abbas; Anam Nigar; Asmat Ali; Arif Ullah (Environmental Geochemistry and Health, 2024)

Comparative genomics of light harvesting chlorophyll (LHC) gene family and impact of chlorophyll-A contents under drought stress in Helianthus annuus - Parwsha Zaib; Hafiz Muhammad Ahmad; Safira Attacha; Mahmood-Ur Rahman; Muhammad Rizwan Shafiq; Kousar Parveen; Sajid Fiaz; Kotb A. Attia; Saira Ishaq; Shazia Arif; Asmaa M. Abushady; Muhammad Jawad Umer (Journal of Plant Physiology, 2023)

Oxidative stress responses of the scleractinian coral Acropora digitifera from the tropical Bidong Island, Malaysia - focus on protein thiol groups' detection - Muhammad Arif Samshuri; Che Din Mohd Safuan; Siti Nurtahirah Jaafar; Chui Pin Leaw; Li Keat Lee; Mathinee Yucharoen; Zainudin Bachok (Journal of Experimental Marine Biology and Ecology, 2023)

Data-driven modeling to predict adsorption of hydrogen on shale kerogen: Implication for underground hydrogen storage - Shams Kalam; Muhammad Arif; Arshad Raza; Najeebullah Lashari; Mohamed Mahmoud (International Journal of Coal Geology, 2023)

Impact of different proportions of sweet potato (Ipomoea batatas L.) flour on physical, chemical and sensory parameters of straight grade flour-based cake rusk - Hafiza Saher Rafique; Ashiq Hussain; Muhammad Nadeem; Abdul Rehman; Tahira Siddique; Ayesha Najam; Haseeb Haroon; Muhammad Rehan Arif; Shazia Yaqub; Haya Fatima; Salah Laaraj (Food and Humanity, 2023)

Development of Aluminium (Al)-Tolerant Soybean Using Molecular Tools: Limitations and Future Directions - Adnan Rasheed; Anwar Ahmad Khan; Muhammad Nawaz; Athar Mahmood; Uzma Arif; Muhammad Umair Hassan; Javed Iqbal; Muhammad Hamzah Saleem; Basharat Ali; Shah Fahad (Journal of Plant Growth Regulation, 2023)

Field response and molecular screening of European wheat germplasm against powdery mildew at the Himalayan region of Pakistan - Aamir Iqbal; Zia Ur Rehman; Muhammad Rameez Khan; Amir Muhammad Khan; Shahid Ullah Khan; Muhammad Arif; Javaid Iqbal; Mujeeb Ur Rehman; Minhaj Ali; Muhammad Qasim; Imran Ali; Zakir Hussain Facho; et al. (Journal of Applied Genetics, 2023)

Heavy metals contamination in vegetables irrigated with wastewater: a case study of underdeveloping regions of Pakistan - Ana Aslam; Asifa Naz; Syed Shahid Hussain Shah; Farah Rasheed; Raheela Naz; Amina Kalsom; Nisa Mukhtar; Abid Niaz; Muhammad Aftab; Irfan Rasheed; Muhammad Arfan Ul Haq; Muhammad Arif; et al. (Environmental Geochemistry and Health, 2023)

Added value upshot of barley amalgamation in wheat flour to boost the physico-chemical quality attributes of flat bread - Muhammad Abdullah; Muhammad Zulkiffal; Tabussam Tufail; Farah Naz Akbar; Muhammad Owais; Javed Ahmed; Ahsan Javed; Muhammad Ijaz Tabassum; Amna Kanwal; Muhammad Asghar; Muhammad Musa; M. A. Rehman Arif; et al. (Cereal Research Communications, 2023)

Genome-wide characterization and expression analysis of cyclic nucleotide-gated ion channels (CNGCs) gene family in Arabidopsis thaliana L. and Helianthus annuus L. for drought stress - Sadaf Oranab; Hafiz Muhammad Ahmad; Sajid Fiaz; Athar Hussain; Muhammad Rizwan; Shazia Arif; Saira Ishaq; Shahnaz Zakia; Asmaa M. Abushady; Itoh Kimiko; Kotb A. Attia (Brazilian Journal of Botany, 2023)

Hydrochemistry, quality, and integrated health risk assessments of groundwater in the Huaibei Plain, China - Jinzhao Xu; Guijian Liu; Ruijia Liu; Wen Si; Miao He; Guanyu Wang; Mingzhen Zhang; Muyuan Lu; Muhammad Arif (Environmental Science and Pollution Research, 2023)

Unlocking the secrets of soil microbes: How decades-long contamination and heavy metals accumulation from sewage water and industrial effluents shape soil biological health - Idrees Haider; Muhammad Arif Ali; Muhammad Sanaullah; Niaz Ahmed; Sajjad Hussain; Muhammad Taimoor Shakeel; Syed Atif Hasan Naqvi; Javeed Shabbir Dar; Mahmoud Moustafa; Mohammed O. Alshaharni (Chemosphere, 2023)

A study on managing plastic waste to tackle the worldwide plastic contamination and environmental remediation - A.K. Priya; M. Muruganandam; Muhammad Imran; Rana Gill; Minnam Reddy Vasudeva Reddy; Mohd Shkir; M.A. Sayed; T.H. AlAbdulaal; H. Algarni; Mohd Arif; Niraj Kumar Jha; Satbir S. Sehgal (Chemosphere, 2023)

Exploring the electrochemical properties of CuSe-decorated NiSe2 nanocubes for battery-supercapacitor hybrid devices - Mudassir Hayat; Yuxue Zhou; Muhammad Zia Ullah Shah; Muhammad Sana ullah; Muhammad Bilal Hanif; Hongying Hou; Umar Arif; Shaukat Khan; Ahmed M. Hassan; Ammar M. Tighezza; Muhammad Sajjad; Raghavender Vadla (Chemosphere, 2023)

Exogenous melatonin mitigates the adverse effects of drought stress in strawberry by upregulating the antioxidant defense system - Muhammad Qaisar Naeem Khan; Nevzat Sevgin; Humaira Rizwana; Nida Arif (South African Journal of Botany, 2023)

Perception of coastal citizens on the prospect of community-based rainwater harvesting system for sustainable water resource management - Mirza Md Tasnim Mukarram; Abdulla - Al Kafy; Mirza Md Tahsin Mukarram; Quazi Umme Rukiya; Abdulaziz I. Almulhim; Anutosh Das; Md. Abdul Fattah; Muhammad Tauhidur Rahman; Md. Arif Chowdhury (Resources, Conservation and Recycling, 2023)

Strategy matters: Phytoremediation potential of native halophytes is jointly associated with their distinct salt tolerances - Songlin Zhang; Xueting Yin; Muhammad Arif; Shanshan Chen; Maohua Ma; Kai Zhu; Qiao Chen; Shengjun Wu; Changxiao Li (Journal of Cleaner Production, 2023)

Influence of surface cleaning on the wettability of calcite/oil/brine systems - Abubakar Isah; Mohamed Mahmoud; Muhammad Arif; Murtada Al Jawad; Abduljamiu O. Amao (Fuel, 2023)

Unraveling the synergy of interface engineering α-MnO2/Bi2WO6 heterostructures and defective active sites for superdurable photocatalysis: Mechanistic insights into charge separation/transfer - Muhammad Arif; Ayaz Mahsud; Amjad Ali; Shipeng Liao; Jiawei Xia; Hai Xiao; Mohammad Azam; Tahir Muhmood; Zhansheng Lu; Yinjuan Chen (Chemical Engineering Journal, 2023)

Elucidating growth and biochemical characteristics of rice seedlings under stress from chromium VI salt and nanoparticles - Maryam Noor; Arif Ullah; Muhammad Israr Khan; Irum Raza; Muhammad Iqbal; Abdul Aziz; Gil Won Kim; Nadia Taimur; Azizullah Azizullah; Imran Ali; Pil Joo Kim (Environmental Science and Pollution Research, 2023)

Metagenomic investigations on antibiotic resistance and microbial virulence in oil-polluted soils from China - Majjid A. Qaria; Chunyan Xu; Arif Hussain; Muhammad Zohaib Nawaz; Daochen Zhu (Environmental Science and Pollution Research, 2023)

Nanocomposite of binary colloids in effective CO2 utilization in porous media for enhanced oil production and wettability alteration - Ravi Shankar Kumar; A.S.K. Sinha; Tushar Sharma; Muhammad Arif (Journal of Environmental Chemical Engineering, 2023)

Mangrove blue carbon stocks estimation in South Sulawesi Indonesia - Abdul Malik; Abd. Rahim; Abd. Rasyid Jalil; Muhammad Fathurachman Amir; Dary Setiawan Arif; Muhammad Rizal; Justikharah Husain; D'rollins William; Nurul Jihad (Continental Shelf Research, 2023)

Edge-hosted CoFeB active sites with graphene nanosheets for highly selective nitrogen reduction reaction towards ambient ammonia synthesis - Muhammad Arif; Anuj Kumar; Muhammad Asim Mushtaq; Umair Azhar; Muhammad Sagir; Muhammad Bilal Tahir; Unaiza Talib; Saira Ajmal; Khalid M. Alotaibi; Ghulam Yasin (Chemical Engineering Journal, 2023)

Immunomodulation, Fish Health and Resistance to Staphylococcus aureus of Nile Tilapia (Oreochromis niloticus) Fed Diet Supplemented with Zinc Oxide Nanoparticles and Zinc Acetate - Atif Yaqub; Muhammad Nasir; Muhammad Kamran; Iqra Majeed; Aneeza Arif (Biological Trace Element Research, 2023)

Metamorphism of Ladakh Island Arc terrain in the Himalayan region: implications from sulfide geochemistry and petrography - Muhammad Farhan; Mohammad Arif; Ying Ye; Chun-Feng Li; Xuegang Chen; Tao Wu; Zaheen Ullah; Syed Ali Turab; Tehseen Zafar; Zahid Hussain; Izhar Sadiq; Mubasir Ali (Arabian Journal of Geosciences, 2023)

Analyzing the non-linear association between urbanization and ecological footprint: an empirical analysis - Muhammad Arif; Abid Rashid Gill; Minhaj Ali (Environmental Science and Pollution Research, 2023)

Data-driven transcriptomics analysis identifies PCSK9 as a novel key regulator in liver aging - Muhammad Arif; Csaba Matyas; Partha Mukhopadhyay; Burhan Yokus; Eszter Trojnar; Janos Paloczi; Bruno Paes-Leme; Suxian Zhao; Falk W. Lohoff; György Haskó; Pal Pacher (GeroScience, 2023)

Investigating symmetrical influence of economic expansion, oil price, and industrial production on trade deficit: a policy pathway toward three neighboring Asian states - Muhammad Bilal Arif; Arshad Mahmood Malik; Gulnaz Hameed; Aadil Hameed Shah; Nigah Hussain; Rabia Shahid (Environmental Science and Pollution Research, 2023)

Preparation and characterization of single perovskite microplates and its sunlight assisted photodecolorization activity, validated by response surface methodology - Arif Nawaz; Irum Naz; Muhammad Atif; Adnan Khan; Nisar Ali (Chemosphere, 2023)

RETRACTED: Sustainable, economical and rapid treatment of multiple lung diseases using therapeutic potential of curcumin nanoparticles - Qudsia Kanwal; Samiah Shahid; Abeel Ahmad; Arif Nazir; Muhammad Yasir; Aneela Anwar; Samar Z. Alshawwa; Munawar Iqbal (Environmental Research, 2023)

Effect of additives in increasing ash fusion temperature during co-firing of coal and palm oil waste biomass - Hariana Hariana; Hafizh Ghazidin; Arif Darmawan; Edi Hilmawan; Prabowo; Muhammad Aziz (Bioresource Technology Reports, 2023)

Unprecedented wildfires in Canada and transboundary effects of carbon monoxide pollution - Awais Shakoor; Taimoor Hassan Farooq; Muhammad Saleem Arif; Sher Muhammad Shahzad (Natural Hazards, 2023)

Effect of heterologous platelet-rich plasma on liver and modulation of glucose metabolism and Wnt signalling pathways in diabetic mice - Amin Arif; Adil Farooq; Muddasir Hassan Abbasi; Muhammad Babar Khawar; Tasleem Akhtar; Humaira Allay Ali; Mehreen Anjum; Rabia Mehmood; Tayyaba Saleem; Nadeem Sheikh (Molecular Biology Reports, 2023)

The Western Himalayan fir tree ring record of soil moisture in Pakistan since 1855 - Zahid Rauf; Nowsherwan Zarif; Adam Khan; Samina Siddiqui; Seerat Fatima; Wahiba Iqbal; Hira Amin; Tahir Iqbal; Muhammad Arif; Shehla Sattar; Muhammad Tahir Rauf (International Journal of Biometeorology, 2023)

Correction: KASP mapping of QTLs for yield components using a RIL population in Basmati rice (Oryza sativa L.) - Hamza Ashfaq; Reena Rani; Naila Perveen; Allah Ditta Babar; Umer Maqsood; Muhammad Asif; Katherine A. Steele; Muhammad Arif (Euphytica, 2023)

Toxicity assessment of heavy metal (Pb) and its bioremediation by potential bacterial isolates - Usaal Tahir; Mariam Zameer; Qurban Ali; Ayesha Rafique; Syeda Maham Ali; Muhammad Umer Arif; Imtiaz Nawaz; Saif ul Malook; Daoud Ali (Environmental Monitoring and Assessment, 2023)

Exogenous Application of Melatonin Improves the Growth and Productivity of Two Broccoli (Brassica oleracea L.) Cultivars Under Salt Stress - Hasan Sardar; Muhammad Arif Ramzan; Safina Naz; Sajid Ali; Shaghef Ejaz; Riaz Ahmad; Muhammad Ahsan Altaf (Journal of Plant Growth Regulation, 2023)

3D and 4D Bioprinting Technologies: A Game Changer for the Biomedical Sector? - Reza Noroozi; Zia Ullah Arif; Hadi Taghvaei; Muhammad Yasir Khalid; Hossein Sahbafar; Amin Hadi; Ali Sadeghianmaryan; Xiongbiao Chen (Annals of Biomedical Engineering, 2023)

Progress in the utilization of water hyacinth as effective biomass material - Asep Bayu Dani Nandiyanto; Risti Ragadhita; Siti Nur Hofifah; Dwi Fitria Al Husaeni; Dwi Novia Al Husaeni; Meli Fiandini; Senny Luckiardi; Eddy Soeryanto Soegoto; Arif Darmawan; Muhammad Aziz (Environment, Development and Sustainability, 2023)
Water hyacinth ( Eichhornia crassipes ) is considered a prospective free-floating aquatic plant potentially used to address current issues on food, energy, and the environment. It can grow quickly and easily in various tropical and subtropical environments as long as it has access to adequate light and water to support photosynthetic growth. Ecosystems are threatened by their invasive growth and remarkable capacity for adaptation. However, managing this plant can result in valuable products. This paper demonstrates particle technologies that might be used to utilize water hyacinths, including brake pads, fertilizer, bioenergy, animal feed, phytoremediation agents, bioplastics, and adsorbents. This study is accompanied by a discussion based on the conducted experiments and currently available literature, providing readers with a clearer understanding. Water hyacinth's capacity to absorb macro- and micro-nutrients, nitrogen, and phosphorus makes it a good plant for phytoremediation. The prospect of producing cellulose makes it prospective as a biomass energy source and livestock feeding. Further, it can be transformed into high-cellulose content particles for applications in bioplastics, brake pads, and adsorbents. The current reports regarding education of water hyacinth to student also were added. Finally, issues and suggestions for future development related to the use of water hyacinths are discussed. This study is expected to provide comprehensive knowledge on how to turn invasive water hyacinth plants into valuable products.

Solar light driven degradation of textile dye contaminants for wastewater treatment – studies of novel polycationic selenide photocatalyst and process optimization by response surface methodology desirability factor - Arif Nawaz; Muhammad Atif; Adnan Khan; Mohsin Siddique; Nisar Ali; Falak Naz; Muhammad Bilal; Tak H. Kim; Malwina Momotko; Hameed Ul Haq; Grzegorz Boczkaj (Chemosphere, 2023)

Spatial-temporal distribution, source identification, risk assessment and water quality assessment of trace elements in the surface water of typical tributary in Yangtze River delta, China - Miao He; Guijian Liu; Yongli Li; Li Zhou; Muhammad Arif; Yuan Liu (Marine Pollution Bulletin, 2023)

Effects of melatonin and Trichoderma harzianum on pak choi yield, chlorophyll contents and antioxidant defense system under clubroot disease - Shazma Gulzar; Muhammad Aamir Manzoor; Fiza Liaquat; Iftikhar Hussain Shah; Asad Rehman; Muhammad Khalid Hameed; Samiah Arif; Xuanwei Zhou; Yidong Zhang (South African Journal of Botany, 2023)

KASP mapping of QTLs for yield components using a RIL population in Basmati rice (Oryza sativa L.) - Hamza Ashfaq; Reena Rani; Naila Perveen; Allah Ditta Babar; Umer Maqsood; Muhammad Asif; Katherine A. Steele; Muhammad Arif (Euphytica, 2023)
Super Basmati is an elite variety with extra-long grains and superior quality but its yield is severely affected by water stress. Recombinant inbred lines (RILs) developed from the cross of Super Basmati and IR55419-04 (a coarse grained variety with high yield potential) were used to identify and map yield-related quantitative trait loci (QTLs) under normal field conditions. Genotypes for 244 KASP markers were obtained from 188 F 9 RILs and a linkage map constructed of 1369.4 cM, with average marker interval of 10.5 cM. Eleven agronomic traits were phenotyped in RILs and parents. Composite interval mapping and inclusive composite interval mapping model identified 21 common QTLs related to nine agronomic traits; of the QTLs identified, twelve mapped at novel positions. LOD scores ranged from 2.51 for number of filled grains ( qFG1.1 ) to 16.8 for plant height ( qPH1.1 ). Four major effect QTLs could explain 20% of variation related for plant height, hundred-grain weight and grain width. Alleles from IR55419-04 improved grain filling, grain weight and grain width, while alleles from Super Basmati contributed to longer grains, panicles and flag leaves. Putative candidate genes were identified for 18 yield-related QTLs. These results validate the use of KASP genotyping for QTL mapping of yield-related traits in a bi-parental segregating population. SNPs in the QTLs identified in this study can be used in marker assisted selection for yield components to improve Basmati rice.

Impregnation of biochar with montmorillonite and its activation for the removal of azithromycin from aqueous media - Muhammad Arif; Guijian Liu; Muhammad Zia ur Rehman; Md Manik Mian; Aniqa Ashraf; Balal Yousaf; Muhammad Saqib Rashid; Rafay Ahmed; Muhammad Imran; Mehr Ahmed Mujtaba Munir (Environmental Science and Pollution Research, 2023)

The diversity of plant communities in different habitats can lead to distinct methanotrophic communities - Li Jiajia; Muhammad Arif; Ding Dongdong; Hu Xin; Gen Qianwen; Yin Fan; Li Changxiao (Rhizosphere, 2023)

Unveiling commodities-financial markets intersections from a bibliometric perspective - Imen Mbarki; Muhammad Arif Khan; Sitara Karim; Andrea Paltrinieri; Brian M. Lucey (Resources Policy, 2023)

Impact of carbonate mineral heterogeneity on wettability alteration potential of surfactants - Ahmed AlZaabi; Muhammad Arif; Mujahid Ali; Ahmed Adila; Yawar Abbas; Ravi Shankar Kumar; Alireza Keshavarz; Stefan Iglauer (Fuel, 2023)

Preparation of Novel Hard Capsule Using Water-Soluble Polysaccharides and Cellulose Nanocrystals for Drug Delivery - Kazharskaia Mariia; Muhammad Arif; Yuanyuan Ding; Zhe Chi; Chenguang Liu (Journal of Pharmaceutical Innovation, 2023)

Endophytic bacterial diversity by 16S rRNA gene sequencing of Pak choi roots under fluazinam, Trichoderma harzianum, and Sophora flavescens inoculation - Shazma Gulzar; Muhammad Aamir Manzoor; Fiza Liaquat; Muhammad Salman Zahid; Samiah Arif; Xuanwei Zhou; Yidong Zhang (Functional & Integrative Genomics, 2023)

Modelling the impact of climate change on dengue outbreaks and future spatiotemporal shift in Pakistan - Alia Saeed; Shaukat Ali; Firdos Khan; Sher Muhammad; Michelle Simões Reboita; Abdul Wali Khan; Muhammad Arif Goheer; Mumtaz Ali Khan; Ramesh Kumar; Aamer Ikram; Aliya Jabeen; Sathirakorn Pongpanich (Environmental Geochemistry and Health, 2023)

Estimation of genetic diversity using seed storage protein (SSP) profiling in wild and cultivated species of Cicer L - Uswah Khalid; Muhammad Qandeel Waheed; Najma Parveen; Mian Abdur Rehman Arif; Anjuman Arif (Molecular Biology Reports, 2023)

Comparison of pollution status and source apportionment for PCBs and OCPs of indoor dust from an industrial city - Mengchen Shen; Guijian Liu; Li Zhou; Hao Yin; Muhammad Arif (Environmental Geochemistry and Health, 2023)

Spinach-derived boron-doped g-C3N4/TiO2 composites for efficient photo-degradation of methylene blue dye - Sadia Faryad; Umair Azhar; Muhammad Bilal Tahir; Wahid Ali; Muhammad Arif; Muhammad Sagir (Chemosphere, 2023)

Fluid source and physicochemical conditions of the polymetallic mineralization in Gawuch Formation, Kohistan Island Arc, NW Pakistan - Muhammad Farhan; Mohammad Arif; Ying Ye; Chun-Feng Li; Xuegang Chen; Dieter Garbe-Schönberg; Tao Wu; Zaheen Ullah; Zahid Hussain; Tehseen Zafar; Izhar Sadiq; Syed Wajid Hanif Bukhari; et al. (Geochemistry, 2023)

Production of fuel oil from elastomer rubber waste via methanothermal liquefaction - Nabeel Ahmad; Nauman Ahmad; Usama Ahmed; Abdul Gani Abdul Jameel; Um-e-Salma Amjad; Murid Hussain; Muhammad Maaz Arif (Fuel, 2023)

Newly formed riparian microhabitats simplify bacterial community structure and diversity - Li Jiajia; Li Lijuan; Muhammad Arif; Ding Dongdong; Hu Xin; Li Changxiao (Journal of Soils and Sediments, 2023)

Assessing the impact of technological innovation on technically derived energy efficiency: a multivariate co-integration analysis of the agricultural sector in South Asia - Dilawar Khan; Muhammad Nouman; Arif Ullah (Environment, Development and Sustainability, 2023)

Bioplastics from waste biomass of marine and poultry industries - Amna Arif; Farrukh Azeem; Ijaz Rasul; Muhammad Hussnain Siddique; Muhammad Zubair; Faizan Muneer; Warda Zaheer; Habibullah Nadeem (Journal of Biosciences, 2023)

Impact of depositional and diagenetic controls on reservoir quality of syn-rift sedimentary systems: An example from Oligocene-Miocene Al Wajh Formation, northwest Saudi Arabia - Abdulwahab Muhammad Bello; Muhammad Naveed Butt; Arif Hussain; Abduljamiu O. Amao; Cornel Olariu; Ardiansyah I. Koeshidayatullah; Muhammad H. Malik; Murtada Al-Hashem; Khalid Al-Ramadan (Sedimentary Geology, 2023)

Enhanced charge separation in dual Z-scheme Au decorated LaFeO3-g-C3N4-BiFeO3 system for efficient H2 production - Nayab Arif; Yunfei Ma; Muhammad Ahsan Iqbal; Muhammad Nadeem Zafar; Huawei Liang; Qitao Zhang; Yu-Jia Zeng (Fuel, 2023)

Screening of salt-tolerant wheat (Triticum aestivum L.) through morphological and molecular markers - Md. Hasanuzzaman; Nihar Ranjan Saha; Sayma Farabi; Md. Tahjib-Ul-Arif; Sabina Yasmin; Muhammad Shahidul Haque (Cereal Research Communications, 2023)

Role of empowering leadership in inducing employee green creative behavior in hotel and restaurant industry: a moderated-moderated mediation model - Muhammad Arif Khattak; Zia Ur Rehman; Shujahat Haider Hashmi (Environment, Development and Sustainability, 2023)

Seasonal variations in water uptake and transpiration for plants in a karst critical zone in China - Hamid M. Behzad; Muhammad Arif; Shihui Duan; Alireza Kavousi; Min Cao; Jiuchan Liu; Yongjun Jiang (Science of The Total Environment, 2023)

Extraction of iron (III) ions by core-shell microgel for in situ formation of iron nanoparticles to reduce harmful pollutants from water - Muhammad Arif (Journal of Environmental Chemical Engineering, 2023)

Chemotaxonomy of reef building corals (family: Acroporidae) via fatty acid biomarkers - Che Din Mohd Safuan; Hock Seng Tan; Muhammad Arif Samshuri; Aminudin Muhammad Afiq-Firdaus; Zainudin Bachok (Biochemical Systematics and Ecology, 2023)

Efficient Regeneration in Sugarcane Using Thin Cell Layer (TCL) Culture System - Aneela Iqbal; Raham Sher Khan; Mubarak Ali Khan; Karim Gul; Muhammad Aizaz; Muhammad Usman; Muhammad Arif (Sugar Tech, 2023)

Evaluation of aerobic biodegradation of phenanthrene using Pseudomonas turukhanskensis: an optimized study - Monika Sharma; El-Sayed Salama; Muhammad Usman; Aman Khan; Muhammad Arif; Xiangkai Li (Biodegradation, 2023)

Development of safe storage guidelines for Kabuli chickpeas - Sheena Malhotra; Muhammad Mudassir Arif Chaudhry; Rani Puthukulangara Ramachandran; Jitendra Paliwal (Journal of Stored Products Research, 2023)

Role of biochar-based free radicals in immobilization and speciation of metals in the contaminated soil-plant environment - Muhammad Saqib Rashid; Guijian Liu; Balal Yousaf; Yasir Hamid; Abdul Rehman; Muhammad Arif; Rafay Ahmed; Yu Song; Aniqa Ashraf (Journal of Environmental Management, 2023)

How does dolomite application affect the greenhouse gases emissions from the terrestrial environment? – A global synthesis - Muhammad Umair Hassan; Maria Batool; Taimoor Hassan Farooq; Muhammad Saleem Arif; Muhammad Aamer; Muhammad Ahmed Waqas; Gadah Albasher; Maryium Sajjad; Awais Shakoor (Fuel, 2023)

Impact of PAM-ZnO nanocomposite on oil recovery - Fatemeh Ozar Asl; Ghasem Zargar; Abbas Khaksar Manshad; Muhammad Arif; Stefan Iglauer; Alireza Keshavarz (Fuel, 2023)

Impact of wettability and injection rate on CO2 plume migration and trapping capacity: A numerical investigation - Haiyang Zhang; Mohammed Al Kobaisi; Muhammad Arif (Fuel, 2023)

Microenvironment engineering of Fe-single-atomic-site with nitrogen coordination anchored on carbon nanotubes for boosting oxygen electrocatalysis in alkaline and acidic media - Abba Bala Musa; Mohammad Tabish; Anuj Kumar; Manickam Selvaraj; Muhammad Abubaker Khan; Badria M. Al-Shehri; Muhammad Arif; Muhammad Asim Mushtaq; Shumaila Ibraheem; Yassine Slimani; Saira Ajmal; Tuan Anh Nguyen; et al. (Chemical Engineering Journal, 2023)

Rational design and modulation strategies of Mo-based electrocatalysts and photo/electrocatalysts towards nitrogen reduction to ammonia (NH3) - Muhammad Arif; Muhammad Babar; Umair Azhar; Muhammad Sagir; Muhammad Bilal Tahir; Muhammad Asim Mushtaq; Ghulam Yasin; Muhammad Mubashir; Jun Wei Roy Chong; Kuan Shiong Khoo; Pau Loke Show (Chemical Engineering Journal, 2023)

Downregulation of NF-κB activation pathways using essential oil derived from Citrus pseudolimon: Anticancer and anti-inflammatory potential - Arfaa Sajid; Qaisar Manzoor; Anam Sajid; Arif Nazir; Muhammad Arsalan Mumtaz; Najum Fatima; Samar Zuhair Alshawwa; Munawar Iqbal; Umer Younas (Biocatalysis and Agricultural Biotechnology, 2023)

Efficient photocatalytic degradation of Rhodamine B dye using solar light-driven La˗Mn co-doped Fe2O3 nanoparticles - Sobia Maqbool; Adeel Ahmed; Arif Mukhtar; Muhammad Jamshaid; Aziz Ur Rehman; Saima Anjum (Environmental Science and Pollution Research, 2023)

Discovering patterns in the topography of existing settlements: the case of the China-Pakistan Economic Corridor (CPEC) route - Ahsen Maqsoom; Bilal Aslam; Umer Khalil; Sheheryar Azam; Zaheer Abbas Kazmi; Muhammad Usman Arif Rana (Arabian Journal of Geosciences, 2023)

Effectiveness of citrus fruit peel as a biosorbent for the mitigation of aflatoxins in vitro - Muhammad Asif Asghar; Farman Ahmed; Mehwish Kamal; Sadia Khan; Muhammad Arif Aghar (Food Additives & Contaminants: Part A, 2022)

Genome wide and evolutionary analysis of heat shock protein 70 proteins in tomato and their role in response to heat and drought stress - Muhammad Zulfiqar Ahmad; Zamarud Shah; Arif Ullah; Shakeel Ahmed; Bushra Ahmad; Afrasyab Khan (Molecular Biology Reports, 2022)

Life cycle assessment of Indonesian canned crab ( Portunus pelagicus ) - Edi Iswanto Wiloso; Muhammad Romli; Bambang Arif Nugraha; Adisa Ramadhan Wiloso; Arief Ameir Rahman Setiawan; Patrik J. G. Henriksson (Journal of Industrial Ecology, 2022)
Indonesia is an archipelagic country with abundant marine wealth that makes it the world's second largest producer of fish after China. While most of Indonesia's capture marine fisheries (80%) are consumed domestically, around 90% of blue swimming crab (BSC) products are exported, mainly in cans. This makes up almost half of all BSC products on the global market, with the United States and the European Union being the main importers. We carried out a life cycle assessment (LCA) of canned BSC products from Indonesia. Our LCA evaluated the production of “one tonne of canned BSC” at market as a functional unit (FU), with a cradle‐to‐market system boundary, encompassing wild capture, preprocessing, processing, and distribution to the port of destination at home and abroad. The processing stage was found to be the highest contributor (hotspot) for most of the impact categories considered, mainly due to the use of tin cans for packaging. Despite producing less by‐catch, BSC caught with traps resulted in around threefold greater global warming impact per FU than those caught using nets. We also concluded that BSC meat produced in Java is environmentally preferable to that from Sumatra, as most of the shells were sold as coproducts. In addition to recycling and substitution of packaging materials, environmental improvements can also be obtained by increasing the number of shell‐processing facilities outside Java. The results of this study can be used by the Indonesian government to develop more sustainable practices to avoid overexploitation of BSC and limit its environmental impacts.

Genetic networks underlying salinity tolerance in wheat uncovered with genome-wide analyses and selective sweeps - Danting Shan; Mohsin Ali; Mohammed Shahid; Anjuman Arif; Muhammad Qandeel Waheed; Xianchun Xia; Richard Trethowan; Mark Tester; Jesse Poland; Francis C. Ogbonnaya; Awais Rasheed; Zhonghu He; et al. (Theoretical and Applied Genetics, 2022)

A Method for Well Logging Identification and Evaluation of Low-Resistivity Gas Hydrate Layers - Huaimin Dong; Jianmeng Sun; Muhammad Arif; Xuefeng Liu; Naser Golsanami; Weichao Yan; Likai Cui; Yihuai Zhang (Pure and Applied Geophysics, 2022)

Correction to: Receptiveness of soil bacterial diversity in relation to soil nutrient transformation and canopy growth in Chinese fir monoculture influenced by varying stand density - Taimoor Hassan Farooq; Uttam Kumar; Yao Yan; Muhammad Saleem Arif; Awais Shakoor; Muhammad Tayyab; Paresh H. Rathod; Muhammad Mohsin Altaf; Pengfei Wu (Trees, 2022)

Genome-wide identification and comparative analysis of MATE gene family in Cucurbitaceae species and their regulatory role in melon (Cucumis melo) under salt stress - Iftikhar Hussain Shah; Muhammad Aamir Manzoor; Irfan Ali Sabir; Muhammad Ashraf; Fazal Haq; Samiah Arif; Muhammad Abdullah; Qingliang Niu; Yidong Zhang (Horticulture, Environment, and Biotechnology, 2022)

Impact of various oviposition substrates on biology of pink bollworm Pectinophora gossypiella (Lepidoptera: Gelechiidae) under laboratory conditions - Shamim Akhtar; Muhammad Jalal Arif; Muhammad Dildar Gogi; Imran ul Haq (International Journal of Tropical Insect Science, 2022)

Sargassum wightii Aqueous Extract Improved Salt Stress Tolerance in Abelmoschus esculentus by Mediating Metabolic and Ionic Rebalance - Zawar Khan; Humaira Gul; Mamoona Rauf; Muhammad Arif; Muhammad Hamayun; Aziz Ud-Din; Zahoor Ahmad Sajid; Sheza Ayaz Khilji; Aliya Rehman; Asma Tabassum; Zahida Parveen; In-Jung Lee (Frontiers in Marine Science, 2022)
Salinity stress has hindered the growth and yield of crops globally. The demands for inducing salt stress tolerance by natural and biological sources with potent antioxidants and growth-promoting metabolites have been the main focus of the recent era. Therefore, the current research was conducted to extract salt stress tolerance-ameliorating metabolites and growth-promoting hormones from the marine brown macroalgae Sargassum wightii Greville ex J. Agardh with maximum antioxidant potential used as a liquid fertilizer for okra ( Abelmoschus esculentus L.). In the current study, the biochemical analysis showed that Sargassum aqueous extract (SAE) was rich in growth-promoting metabolites, antioxidants, and hormones. Meanwhile, overaccumulation of glycine betaine attracted the focus of the current research dealing with salt stress tolerance amelioration in A. esculentus . The plants supplemented with SAE (2% and 4%) and 0.04% ascorbic acid (AsA) alone and in combinations were subjected to sodium salt stress (NaCl; 75 mM). Results revealed that SAE efficiently promoted the vegetative and reproductive growth of plants by elevating the growth-promoting metabolites and hormones in comparison to control plants. Ionic contents (Na + , K + , Ca 2+ , and Mg 2+ ) and ratios (K + /Na + , Mg 2+ /Na + , and Ca 2+ /Na + ) were modulated in SAE-treated plants. SAE also increased the level of carbohydrates, proteins, lipids, carotenoids, and proline and decreased the level of hydrogen peroxide and abscisic acid in salt-treated plants compared with the control groups. Enzymatic activities of catalase, ascorbate peroxidase, and guaiacol peroxidase were also enhanced by SAE treatment upon salt stress. The SAE-mediated stress tolerance amelioration and the positive growth response of A. esculentus were further accelerated by AsA (0.04%) supplementation used in combination with SAE (2% and 4%). The current study revealed a novel report of the antioxidant and metabolite-rich algal extract ( S. wightii ) formulation along with AsA that induced salt stress tolerance and promoted the overall growth performance of A. esculentus by rebalancing the ionic and metabolic status.

Receptiveness of soil bacterial diversity in relation to soil nutrient transformation and canopy growth in Chinese fir monoculture influenced by varying stand density - Taimoor Hassan Farooq; Uttam Kumar; Yao Yan; Muhammad Saleem Arif; Awais Shakoor; Muhammad Tayyab; Paresh H. Rathod; Muhammad Mohsin Altaf; Pengfei Wu (Trees, 2022)

Correction to: Cannabinoid receptor 2 activation alleviates diabetes-induced cardiac dysfunction, inflammation, oxidative stress, and fibrosis - Mohanraj Rajesh; Partha Mukhopadhyay; Sándor Bátkai; Muhammad Arif; Zoltán V. Varga; Csaba Mátyás; Janos Paloczi; Andrea Lehocki; György Haskó; Pal Pacher (GeroScience, 2022)

Cannabinoid receptor 2 activation alleviates diabetes-induced cardiac dysfunction, inflammation, oxidative stress, and fibrosis - Mohanraj Rajesh; Partha Mukhopadhyay; Sándor Bátkai; Muhammad Arif; Zoltán V. Varga; Csaba Mátyás; Janos Paloczi; Andrea Lehocki; György Haskó; Pal Pacher (GeroScience, 2022)

Monitoring land use land cover changes and its impacts on land surface temperature over Mardan and Charsadda Districts, Khyber Pakhtunkhwa (KP), Pakistan - Rehan Khan; Huan Li; Muhammad Basir; Yuan Lin Chen; Meer Muhammad Sajjad; Ihtisham Ul Haq; Barkat Ullah; Muhammad Arif; Waqas Hassan (Environmental Monitoring and Assessment, 2022)

Collaborative-trust approach toward malicious node detection in vehicular ad hoc networks - Shahid Sultan; Qaisar Javaid; Arif Jamal Malik; Fadi Al-Turjman; Muhammad Attique (Environment, Development and Sustainability, 2022)

Development of Basmati lines by the introgression of three bacterial blight resistant genes through marker-assisted breeding - Allah Ditta Babar; Abha Zaka; Shahzad Amir Naveed; Niaz Ahmad; Kashif Aslam; Muhammad Asif; Umer Maqsood; Casiana M. Vera Cruz; Muhammad Arif (Euphytica, 2022)

Phyto-mediated photocatalysis: a critical review of in-depth base to reactive radical generation for erythromycin degradation - Aniqa Ashraf; Guijian Liu; Balal Yousaf; Muhammad Arif; Rafay Ahmed; Audil Rashid; Luqman Riaz; Muhammad Saqib Rashid (Environmental Science and Pollution Research, 2022)

Screening clonally replicated Acacia mangium breeding populations for tolerance to Ceratocystis canker and wilt disease - Jeremy Todd Brawner; Sri Sunarti; Arif Nirsatmanto; Heru Indrayadi; Marthin Tarigan; Muhammad Yuliarto; Sri Rahayu; Eko Bhakti Hardiyanto; Morag Glen; Caroline Mohammed; Anto Rimbawanto (Tree Genetics & Genomes, 2022)
Three screening trials of clonally replicated Acacia mangium seedlings were evaluated for survival and lesion length following inoculation with locally collected strains of Ceratocystis in Indonesia. Tolerance in the population was low with 6.7% of the 1033 clones represented by more than 4 ramets surviving repeated inoculations. Differences in tolerance among populations were slight; however, populations with consistently higher survival and shorter lesion lengths were from Papua New Guinea rather than Queensland. Estimates of the proportion of the experimental variation attributable to differences among parents (heritability) were low to moderate for both survival and lesion length. Estimates of the proportion of the experimental variation that was attributable to differences among clones (repeatability) were greater but typically similar to the heritability estimates, indicating that initial improvements from selection will primarily be derived from identifying tolerant parents. While genetic correlations among experiments were positive, estimates could not exclude the existence of host–pathogen interactions. Two validation trials of the tolerant clones were assessed 9 months after establishment; these trials verified that one-third of the clones identified in the nursery screening were also tolerant to Ceratocystis in field trials. The experiments confirmed that nursery screening may be used to quickly focus efforts on parents that produce more tolerant progeny, screening additional seedlings to increase selection intensity rather than using clonal replication to increase accuracy would lead to greater improvements in tolerance and field trials are required to verify disease tolerance at later ages.

Serum Stable and Low Hemolytic Temporin-SHa Peptide Analogs Disrupt Cell Membrane of Methicillin-Resistant Staphylococcus aureus (MRSA) - Rukesh Maharjan; Arif Iftikhar Khan; Muhammad Nadeem-ul-Haque; Marc Maresca; M. Iqbal Choudhary; Farzana Shaheen; Shabana U. Simjee (Probiotics and Antimicrobial Proteins, 2022)

Biorational approach for management of whitefly, Bemisia tabaci (Gennadius) (Homoptera: Aleyrodidae), on cotton crop - Muhammad Iqbal; Muhammad Jalal Arif; Shafqat Saeed; Mansoor ul Hasan; Nazir Javed (International Journal of Tropical Insect Science, 2022)

Range extension and species confirmation of Rhyneptesicus nasutus (Sind Serotine Bat) (Mammalia:Chiroptera) from Bajaur Agency, FATA, Pakistan - Muhammad Idnan; Sajid Mansoor; Muhammad Babar Khawar; Arshad Javid; Ali Hussain; Muhammad Imran; Arif Ullah (Molecular Biology Reports, 2022)

Purification and functional characterization of lectin from Chenopodium album - Mahwish Javed; Muhammad Bilal; Bushra Tabassum; Arif Malik; Olawale Samuel Adeyinka; Muhammad Tariq; Idrees Ahmad Nasir (Journal of Proteins and Proteomics, 2022)

Structural and Functional Annotation of Napin-Like Protein from Momordica charantia to Explore its Medicinal Importance - Rawaba Arif; Muhammad Anjum Zia; Ghulam Mustafa (Biochemical Genetics, 2022)

Gibberellic acid and urease inhibitor optimize nitrogen uptake and yield of maize at varying nitrogen levels under changing climate - Ikram Ullah; Khadim Dawar; Muhammad Tariq; Muhammad Sharif; Shah Fahad; Muhammad Adnan; Haroon Ilahi; Taufiq Nawaz; Mukhtar Alam; Aman Ullah; Muhammad Arif (Environmental Science and Pollution Research, 2022)

Correction to: Automation in Agriculture by Machine and Deep Learning Techniques: A Review of Recent Developments - Muhammad Hammad Saleem; Johan Potgieter; Khalid Mahmood Arif (Precision Agriculture, 2021)

Automation in Agriculture by Machine and Deep Learning Techniques: A Review of Recent Developments - Muhammad Hammad Saleem; Johan Potgieter; Khalid Mahmood Arif (Precision Agriculture, 2021)

Hydrogen Sulfide: A Novel Gaseous Molecule for Plant Adaptation to Stress - Mukhtar Ahmed; Shah Fahad; Muhammad Arif Ali; Sajjad Hussain; Muhammad Tariq; Fariha Ilyas; Shakeel Ahmad; Shah Saud; Hafiz Mohkum Hammad; Wajid Nasim; Chao Wu; Hongyan Liu (Journal of Plant Growth Regulation, 2021)

Genetic basis of some physiological traits and yield in early and late sowing conditions in bread wheat (Triticum aestivum L.) - Mian Abdur Rehman Arif; Maryam Liaqat; Muhammad Imran; Muhammad Qandeel Waheed; Anjuman Arif; Sukhwinder Singh; Sajid Shokat (Journal of Applied Genetics, 2021)

Physiological Response of Shallow-Water Hard Coral Acropora digitifera to Heat Stress via Fatty Acid Composition - Che Din Mohd Safuan; Muhammad Arif Samshuri; Siti Nurtahirah Jaafar; Chun Hong Tan; Zainudin Bachok (Frontiers in Marine Science, 2021)
Heat stress disturbs the mutualistic relationship between the hard corals and the symbiotic algae, which cause coral bleaching. A wide array of biochemical parameters is used to demonstrate the phenomenon. This study exposed a shallow-water hard coral, Acropora digitifera , to a series of elevated temperatures over time while the interaction between Symbiodiniaceae (SD) density, antioxidants activities, fatty acid (FA) composition, and putative FA health indicators was evaluated. Heat stress caused a substantial loss in SD densities, consequently regulated the antioxidant activities and caused significant changes in FA composition. There was a lack of evidence showing A. digitifera experienced oxidative stress; nonetheless, a significant decrease of monounsaturated fatty acid as (MUFA) and polyunsaturated fatty acid (PUFA) during the thermally induced experiment demonstrated that corals utilize their unsaturated FA as a final barrier or as a repair system against oxidative damage once the antioxidant enzyme cannot cope with stress condition. The lower ratio of putative FA health indicators [i.e., n-3 LC:n-6 LC, eicosapentaenoic acid (EPA):arachidonic acid (ARA), and docosahexaenoic acid (DHA):ARA] characterized an unhealthy coral. The loss of SD density was significantly correlated with certain PUFA markers [i.e., linolenic acid (18:3n6), 20:5n3, and 22:6n3] and putative FA health indicator (i.e., n-3 LC:n-6 LC, EPA:ARA, and DHA:ARA). These notably imply that the FA linked with the symbiont can be a potential health indicator for assessing the effect of the environmental stressor on coral. This study also revealed the regulation of FAs during stress conditions, especially when heterotrophic feeding is limited. Future studies on FA profiles toward antagonistic or synergistic effects will offer a better understanding of the nature of this relationship under a harsh climate.

Correction to: influence of foliar glutathione and putrescine on metabolism and mineral status of genetically diverse rapeseed cultivars under hexavalent chromium stress - Almas Jahan; Muhammad Iqbal; Fahad Shafiq; Arif Malik; Muhammad Tariq Javed (Environmental Science and Pollution Research, 2021)

Influence of foliar glutathione and putrescine on metabolism and mineral status of genetically diverse rapeseed cultivars under hexavalent chromium stress - Almas Jahan; Muhammad Iqbal; Fahad Shafiq; Arif Malik; Muhammad Tariq Javed (Environmental Science and Pollution Research, 2021)

Adoption of green banking practices and environmental performance in Pakistan: a demonstration of structural equation modelling - Alam Rehman; Irfan Ullah; Fakhr-e-Alam Afridi; Zain Ullah; Muhammad Zeeshan; Arif Hussain; Haseeb Ur Rahman (Environment, Development and Sustainability, 2021)

Individual Rather Than Simultaneous Priming with Glutathione and Putrescine Reduces Chromium Cr6+ Toxicity in Contrasting Canola (Brassica napus L.) Cultivars - Almas Jahan; Muhammad Iqbal; Arif Malik (Bulletin of Environmental Contamination and Toxicology, 2021)

Combining Landsat-8 spectral bands with ancillary variables for land cover classification in mountainous terrains of northern Pakistan - Arif Ur Rehman; Sami Ullah; Muhammad Shafique; Muhammad Sadiq Khan; Muhammad Tariq Badshah; Qi-jing Liu (Journal of Mountain Science, 2021)

Foliar Manganese Supply Enhances Crop Productivity, Net Benefits, and Grain Manganese Accumulation in Direct-Seeded and Puddled Transplanted Rice - Usman Zulfiqar; Saddam Hussain; Muhammad Ishfaq; Nauman Ali; Muhammad Umair Yasin; Muhammad Arif Ali (Journal of Plant Growth Regulation, 2021)

The convergence of species composition along the drawdown zone of the Three Gorges Dam Reservoir, China: implications for restoration - Jie Zheng; Muhammad Arif; Songlin Zhang; Zhongxun Yuan; Limiao Zhang; Zhi Dong; Xue Tan; Wokadala Charles; Changxiao Li (Environmental Science and Pollution Research, 2021)

HEC-RAS and GIS-based flood plain mapping: A case study of Narai Drain Peshawar - Awais Salman; Sher Shah Hassan; Gul Daraz Khan; Muhammad Arif Goheer; Aftab Ahmad Khan; Khurram Sheraz (Acta Geophysica, 2021)

Epidemiology of molecular probes in Xpert MTB/RIF assay in Khyber Pakhtunkhwa, Pakistan - Anwar Sheed Khan; Muhammad Tahir Khan; Sajid Ali; Taj Ali Khan; Muhammad Qasim; Arif Malik; Sajid Ali; Wasim Sajjad; Qurrat ul ain; Muhammad Irfan (Archives of Microbiology, 2021)

The impacts of land use/land cover changes on the supply-demand budget of urban ecosystem services - Syed Atif Bokhari; Zafeer Saqib; Amjad Ali; Arif Mahmud; Nadia Akhtar; Ambrina Kanwal; Muhammad Zaman ul Haq (Arabian Journal of Geosciences, 2021)

Chemical composition of gemstones and characterization of their host pegmatites and country rocks from Chumar Bakhoor, Gilgit-Baltistan, Pakistan: implications for the source of gem-forming fluids - Amjad Hussain; Muhammad Tahir Shah; Mohammad Arif; Muhammad Hassan Agheem; Muhammad Saleem Mughal; Shakir Ullah; Syed Asim Hussain; Izhar Sadiq (Arabian Journal of Geosciences, 2021)

Modeling and Monitoring Wheat Crop Yield Using Geospatial Techniques: A Case Study of Potohar Region, Pakistan - Sher Shah Hassan; Muhammad Arif Goheer (Journal of the Indian Society of Remote Sensing, 2021)

Assessment of pathogenicity of Beauveria bassiana, Metarhizium anisopliae, Verticillium lecanii and Bacillus thuringiensis var. kurstaki against Bactrocera cucurbitae Coquillett (Diptera: Tephritidae) via diet-bioassay technique under controlled conditions - Mubashar Iqbal; Muhammad Dildar Gogi; Bilal Atta; Muhammad Junaid Nisar; Muhammad Jalal Arif; Nazir Javed (International Journal of Tropical Insect Science, 2021)

Comparing different space-borne sensors and methods for the retrieval of land surface temperature - Arif UR Rehman; Sami Ullah; Qijing Liu; Muhammad Sadiq Khan (Earth Science Informatics, 2021)

Removal of N-terminal methionine of human interferon α-2b by co‐producing with Pyrococcus furiosus methionine aminopeptidase in Escherichia coli - Amina Arif; Naeem Rashid; Muhammad Akhtar (Biologia, 2021)

First report of potato wilt caused by Plectosphaerella cucumerina in Pakistan - Muhammad Waqar Alam; Arif Malik; Abdul Rehman; Mubeen Sarwar; Saira Mehboob (Journal of Plant Pathology, 2021)

First report of white mould of potato caused by Sclerotinia sclerotiorum in Pakistan - Muhammad Waqar Alam; Abdul Rehman; Arif Malik; Saira Mehboob; Mubeen Sarwar; Sher Muhammad (Journal of Plant Pathology, 2021)

P53-mediated in vitro inhibition of PhIP-induced oxidative damage by myricetin bulk and nano forms in healthy lymphocytes - Shabana Akhtar; Diana Anderson; Talha Muhammad Azam; Arif Malik (Archives of Toxicology, 2021)

Phytosynthesis of poly (ethylene glycol) methacrylate-hybridized gold nanoparticles from C. tuberculata: their structural characterization and potential for in vitro growth in banana - Natasha Anwar; Jan Wahid; Jalal Uddin; Abbas Khan; Mohib Shah; Syed Adil Shah; Fazle Subhan; Mubarak Ali Khan; Kazim Ali; Mamoona Rauf; Muhammad Arif (In Vitro Cellular & Developmental Biology - Plant, 2021)

Biochar and leguminous cover crops as an alternative to summer fallowing for soil organic carbon and nutrient management in the wheat-maize-wheat cropping system under semiarid climate - Muhammad Arif; Ikramullah; Talha Jan; Muhammad Riaz; Kashif Akhtar; Salman Ali; Shahen Shah; Fazal Jalal; Ishaq A. Mian; Khadim Muhammad Dawar; Haiyan Wang (Journal of Soils and Sediments, 2021)

Influence of abiotic factors on population dynamics of SOGATELLA FURCIFERA HORVATH (DELPHACIDAE: HOMOPTERA) - Ijaz Haider; Muhammad Sufyan; Muhammad Akhtar; Muhammad Jalal Arif (International Journal of Tropical Insect Science, 2021)

Nutritional Value, Phytochemical Profile, Antioxidant Property and Agar Yielding Potential of Macroalgae from Coasts of Cox’s Bazar and St. Martin’s Island of Bangladesh - Md. Tahmeed Hossain; Abdullah Al Mamun Sohag; Md. Nazmul Haque; Md. Tahjib-Ul-Arif; Raju Dash; Muhammad Tanvir Hossain Chowdhury; Md. Afzal Hossain; Il Soo Moon; Md. Abdul Hannan (Journal of Aquatic Food Product Technology, 2021)

Investigation of in vivo anti-inflammatory and anti-angiogenic attributes of coumarin-rich ethanolic extract of Melilotus indicus - Mohammad Saleem; Muhammad Asif; Anum Parveen; Hafiza Sidra Yaseen; Malik Saadullah; Asiya Bashir; Jawaria Asif; Mehwish Arif; Ikram Ullah Khan; Rizwan Ullah Khan (Inflammopharmacology, 2021)

Approaches to prevent and control Campylobacter spp. colonization in broiler chickens: a review - Mohamed E. Abd El-Hack; Mohamed T. El-Saadony; Abdelrazeq M. Shehata; Muhammad Arif; Vinod K. Paswan; Gaber El-Saber Batiha; Asmaa F. Khafaga; Ahmed R. Elbestawy (Environmental Science and Pollution Research, 2021)

Emission profile of Pakistan’s agriculture: past trends and future projections - Muhammad Ijaz; Muhammad Arif Goheer (Environment, Development and Sustainability, 2021)

Future climatic changes, extreme events, related uncertainties, and policy recommendations in the Hindu Kush sub-regions of Pakistan - Shaukat Ali; Alia Saeed; Rida Sehar Kiani; Sher Muhammad; Firdos Khan; Romaisa Babar; Asif Khan; Muhammad Shahid Iqbal; Muhammad Arif Goheer; Wajid Naseem; Shah Fahad (Theoretical and Applied Climatology, 2021)

Dihydropyrimidones: A ligands urease recognition study and mechanistic insight through in vitro and in silico approach - Farman Ali Khan; Shahbaz Shamim; Nisar Ullah; Muhammad Arif Lodhi; Khalid Mohammed Khan; Kanwal; Farman Ali; Sahib Gul Afridi; Shahnaz Perveen; Ajmal Khan (Medicinal Chemistry Research, 2021)

Higher biochar rate strongly reduced decomposition of soil organic matter to enhance C and N sequestration in nutrient-poor alkaline calcareous soil - Samar Fatima; Muhammad Riaz; Mohammad I. Al-Wabel; Muhammad Saleem Arif; Tahira Yasmeen; Qaiser Hussain; Mahnaz Roohi; Shah Fahad; Kawsar Ali; Muhammad Arif (Journal of Soils and Sediments, 2021)

SARS-CoV-2 nucleocapsid and Nsp3 binding: an in silico study - Muhammad Tahir Khan; Muhammad Tariq Zeb; Hina Ahsan; Abrar Ahmed; Arif Ali; Khalid Akhtar; Shaukat Iqbal Malik; Zhilei Cui; Sajid Ali; Anwar Sheed Khan; Manzoor Ahmad; Dong-Qing Wei; et al. (Archives of Microbiology, 2021)

Influence of IP-injected ZnO-nanoparticles in Catla catla fish: hematological and serological profile - Tariq Munir; Muhammad Latif; Arslan Mahmood; Arif Malik; Fahad Shafiq (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Microalgae Isolation for Nutrient Removal Assessment and Biodiesel Production - Muhammad Arif; Le Wang; El-Sayed Salama; Mian Sabir Hussain; Xiangkai Li; Mohammed Jalalah; M. S. Al-Assiri; Farid A. Harraz; Min-Kyu Ji; Pu Liu (BioEnergy Research, 2020)

Effect of silicon on tritrophic interaction of cotton, Gossypium hirsutum (Linnaeus), Bemisia tabaci (Gennadius) (Homoptera: Aleyrodidae) and the predator, Chrysoperla carnea (Stephens) (Neuroptera: Chrysopidae) - Asim Abbasi; Muhammad Sufyan; Muhammad Jalal Arif; Shahbaz Talib Sahi (Arthropod-Plant Interactions, 2020)

A review on phyto pharmacological, botanical and marketed formulation studies of Anethum sowa - Sangeeta Singh; Mohammad Khalid; Muhammad Arif; Farogh Ahsan (Advances in Traditional Medicine, 2020)

Enhanced uptake of Cd, Cr, and Cu in Catharanthus roseus (L.) G.Don by Bacillus cereus: application of moss and compost to reduce metal availability - Muhammad Umair Mushtaq; Ameena Iqbal; Ismat Nawaz; Cyrus Raza Mirza; Sohail Yousaf; Ghazanfar Farooq; Muhammad Arif Ali; Aqib Hassan Ali Khan; Mazhar Iqbal (Environmental Science and Pollution Research, 2020)

Molecular and morphological discrimination of Chrysanthemum indicum using allele-specific PCR and T-shaped trichome - Suleman Abid; Lalitha Kaliraj; Muhammad Huzaifa Arif; Joon Hurh; Jong Chan Ahn; Deok Chun Yang; Seok-Kyu Jung (Molecular Biology Reports, 2020)

Performance Analysis of Combined Cycle with Air Breathing Derivative Gas Turbine, Heat Recovery Steam Generator, and Steam Turbine as LNG Tanker Main Engine Propulsion System - Wahyu Nirbito; Muhammad Arif Budiyanto; Robby Muliadi (Journal of Marine Science and Engineering, 2020)
This study explains the performance analysis of a propulsion system engine of an LNG tanker using a combined cycle whose components are gas turbine, steam turbine, and heat recovery steam generator. The researches are to determine the total resistance of an LNG tanker with a capacity of 125,000 m3 by using the Maxsurf Resistance 20 software, as well as to design the propulsion system to meet the required power from the resistance by using the Cycle-Tempo 5.0 software. The simulation results indicate a maximum power of the system of about 28,122.23 kW with a fuel consumption of about 1.173 kg/s and a system efficiency of about 48.49% in fully loaded conditions. The ship speed can reach up to 20.67 knots.

Attraction and retention-period of different stuffs and stuffing techniques with their active food baits for the management of peach fruit fly, Bactrocera zonata (Diptera: Tephritidae) - Muhammad Junaid Nisar; Muhammad Dildar Gogi; Muhammad Jalal Arif; Shahbaz Talib Sahi (International Journal of Tropical Insect Science, 2020)

Risk Assessment of Work Accident in Container Terminals Using the Fault Tree Analysis Method - Muhammad Arif Budiyanto; Haris Fernanda (Journal of Marine Science and Engineering, 2020)
The use of containers in the world is increasing every year in line with international trade flows. In very complex container terminal operations, the risk of work accidents is inevitable and can happen at any time. Therefore, this paper aimed to identify accidents and potential risks occurring in the container terminals. For the case study, the analysis was used the data of accidents during five years in one of the major container terminals in Indonesia. Risk assessment is carried out using the risk matrix method to get the level of risk. The risk that has the highest level is analyzed by using the Fault Tree Analysis method. From the results of the risk assessment shows the container fell to the berth when loading and unloading have the highest risk value. While the results of the Fault Tree Analysis show that traffic accidents are the biggest potential risk, which is 41.8% compared to other accidents. Moreover, human factors especially due to the negligence in operating vehicles or equipment as well as the damage of equipment were the highest common causes of accidents in the container terminal. Based on these results the contribution offered is the risk control options for terminal operators to reduce the possibility of safety failure in the container terminal.

Effect of biochar and phosphate solubilizing bacteria on growth and phosphorus uptake by maize in an Aridisol - Muhammad Arif Ali; Muhammad Mustansar Ajaz; Muhammad Rizwan; Muhammad Farooq Qayyum; Muhammad Arshad; Sajjad Hussain; Niaz Ahmad; Muhammad Amjad Qureshi (Arabian Journal of Geosciences, 2020)

NaCl improved Cd tolerance of the euhalophyte Suaeda glauca but not the recretohalophyte Limonium aureum - Songlin Zhang; Xilu Ni; Muhammad Arif; Jie Zheng; Annastacia Stubbs; Changxiao Li (Plant and Soil, 2020)

Association of intronic polymorphisms (rs1549339, rs13402242) and mRNA expression variations in PSMD1 gene in arsenic-exposed workers - Saqiba Ahmad; Bushra Arif; Zertashia Akram; Malik Waqar Ahmed; Asad Ullah Khan; Muhammad Zahid Hussain; Faisal Rahman; Mahmood Akhtar Kayani; Ishrat Mahjabeen (Environmental Science and Pollution Research, 2020)

Implication of Physiological and Biochemical Variables of Prognostic Importance in Lead Exposed Subjects - Arif Malik; Muhammad Abdul Basit Ashraf; Muhammad Waqas Khan; Ayesha Zahid; Hassan Shafique; Sulayman Waquar; Siew Hua Gan; Muhammad Ashraf (Archives of Environmental Contamination and Toxicology, 2020)

Approaches in Enhancing Thermotolerance in Plants: An Updated Review - Shafaqat Ali; Muhammad Rizwan; Muhammad Saleem Arif; Rehan Ahmad; Mirza Hasanuzzaman; Basharat Ali; Afzal Hussain (Journal of Plant Growth Regulation, 2020)

Nanozymes for medical biotechnology and its potential applications in biosensing and nanotherapeutics - Samman Munir; Asad Ali Shah; Hazir Rahman; Muhammad Bilal; Muhammad Shahid Riaz Rajoka; Abdul Arif Khan; Mohsin Khurshid (Biotechnology Letters, 2020)

An effective modification of finite element method for heat and mass transfer of chemically reactive unsteady flow - Yasir Nawaz; Muhammad Shoaib Arif (Computational Geosciences, 2020)

Inhibition of Hyperuricemia and Gouty Arthritis in BALB/c Mice Using Copper Oxide Nanoparticles - Mubin Mustafa Kiyani; Hamza Rehman; Mir Arif Hussain; Saira Jahan; Muhammad Afzal; Irum Nawaz; Tariq Mahmood; Syed Ali Imran Bokhari (Biological Trace Element Research, 2020)

Spatio-Temporal Variability of Summer Monsoon Onset over Pakistan - Shaukat Ali; Bushra Khalid; Rida Sehar Kiani; Romaisa Babar; Sana Nasir; Nadia Rehman; Muhammad Adnan; Muhammad Arif Goheer (Asia-Pacific Journal of Atmospheric Sciences, 2020)

First report of brown rot caused by Rhizopus arrhizus on tomato in Pakistan - Fiza Liaquat; Qunlu Liu; Samiah Arif; Iftikhar Hussain Shah; Hassan Javed Chaudhary; Muhammad Farooq Hussain Munis (Journal of Plant Pathology, 2019)

Different nitrogen and biochar sources’ application in an alkaline calcareous soil improved the maize yield and soil nitrogen retention - Muhammad Farooq Qayyum; Mehak Ameer Abdullah; Muhammad Rizwan; Ghulam Haider; Muhammad Arif Ali; Muhammad Zafar-ul-Hye; Muhammad Abid (Arabian Journal of Geosciences, 2019)

Genome-wide variation patterns between landraces and cultivars uncover divergent selection during modern wheat breeding - Jindong Liu; Awais Rasheed; Zhonghu He; Muhammad Imtiaz; Anjuman Arif; Tariq Mahmood; Abdul Ghafoor; Sadar Uddin Siddiqui; Muhammad Kashif Ilyas; Weie Wen; Fengmei Gao; Chaojie Xie; et al. (Theoretical and Applied Genetics, 2019)

Putative impacts of phytogenic additives to ameliorate lead toxicity in animal feed - Mohamed E. Abd El-Hack; Sameh A. Abdelnour; Abd El-Moneim E. Abd El-Moneim; Muhammad Arif; Asmaa Khafaga; Hazem Shaheen; Dalia Samak; Ayman A. Swelum (Environmental Science and Pollution Research, 2019)

N-Pyrazoloyl and N-thiopheneacetyl hydrazone of isatin exhibited potent anti-inflammatory and anti-nociceptive properties through suppression of NF-κB, MAPK and oxidative stress signaling in animal models of inflammation - Sara Zeeshan; Muhammad Naveed; Adnan Khan; Ayesha Atiq; Maryam Arif; Muhammad Naeem Ahmed; Yeong Shik Kim; Salman Khan (Inflammation Research, 2019)

Residues of endosulfan in cotton growing area of Vehari, Pakistan: an assessment of knowledge and awareness of pesticide use and health risks - Ashfaq Ahmad; Muhammad Shahid; Sana Khalid; Habiba Zaffar; Tatheer Naqvi; Arshid Pervez; Muhammad Bilal; Muhammad Arif Ali; Ghulam Abbas; Wajid Nasim (Environmental Science and Pollution Research, 2019)

Retraction Note to: Support vector regression methodology for prediction of output energy in rice production - Marziye Yousefi; Benyamin Khoshnevisan; Shahaboddin Shamshirband; Shervin Motamedi; Mohd Hairul Nizam Md. Nasir; Muhammad Arif; Rodina Ahmad (Stochastic Environmental Research and Risk Assessment, 2019)

Assessment of Circulating Biochemical Markers in Mice Receiving Cinnamon and Glycyrrhizin Under Carbon Tetrachloride Induced Hepatic Injury - Mahmood Rasool; Arif Malik; Sadia Saleem; Shakeel Ahmed Ansari; Javed Iqbal; Muhammad Asif; Mohammed Amjad Kamal; Mohammed Hussain Al-Qahtani; Sajjad Karim (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2019)

The Arabidopsis nucleoporin NUP1 is essential for megasporogenesis and early stages of pollen development - Shuguang Bao; Guangshuang Shen; Guichen Li; Zhikang Liu; Muhammad Arif; Qingqing Wei; Shuzhen Men (Plant Cell Reports, 2019)

Extremely stable indole-3-glycerol-phosphate synthase from hyperthermophilic archaeon Pyrococcus furiosus - Muhammad Arif; Naeem Rashid; Sumera Perveen; Qamar Bashir; Muhammad Akhtar (Extremophiles, 2019)

5-Aminolevulinic Acid-Induced Heavy Metal Stress Tolerance and Underlying Mechanisms in Plants - Shafaqat Ali; Muhammad Rizwan; Abbu Zaid; Muhammad Saleem Arif; Tahira Yasmeen; Afzal Hussain; Muhammad Rizwan Shahid; Syed Asad Hussain Bukhari; Saddam Hussain; Ghulam Hassan Abbasi (Journal of Plant Growth Regulation, 2018)

Sesbagrandiflorain A and B: isolation of two new 2-arylbenzofurans from the stem bark of Sesbania grandiflora - Noviany Noviany; Arif Nurhidayat; Sutopo Hadi; Tati Suhartati; Muhammad Aziz; Neny Purwitasari; Iman Subasman (Natural Product Research, 2018)

Re-thinking the unimpeded tube-well growth under the depleting groundwater resources in the Punjab, Pakistan - Muhammad Arif Watto; Amin W. Mugera; Ross Kingwell; Muhammad Mudasar Saqab (Hydrogeology Journal, 2018)

Role of sorption energy and chemisorption in batch methylene blue and Cu2+ adsorption by novel thuja cone carbon in binary component system: linear and nonlinear modeling - Saeed Rehman; Adnan Adil; Ahsan Jabbar Shaikh; Jehanzeb Ali Shah; Muhammad Arshad; Muhammad Arif Ali; Muhammad Bilal (Environmental Science and Pollution Research, 2018)

The application of gene marker-assisted selection and proteomics for the best meat quality criteria and body measurements in Qinchuan cattle breed - Mohamed E. Abd El-Hack; Sameh A. Abdelnour; Ayman A. Swelum; Muhammad Arif (Molecular Biology Reports, 2018)

Potentially toxic elements in soil of the Khyber Pakhtunkhwa province and Tribal areas, Pakistan: evaluation for human and ecological risk assessment - Umar Saddique; Said Muhammad; Mohsin Tariq; Hua Zhang; Mohammad Arif; Ishtiaq A. K. Jadoon; Nimat Ullah Khattak (Environmental Geochemistry and Health, 2018)

Novel candidate genes and variants underlying autosomal recessive neurodevelopmental disorders with intellectual disability - Regie Lyn P. Santos-Cortez; Valeed Khan; Falak Sher Khan; Zaib-un-Nisa Mughal; Imen Chakchouk; Kwanghyuk Lee; Memoona Rasheed; Rifat Hamza; Anushree Acharya; Ehsan Ullah; Muhammad Arif Nadeem Saqib; Izoduwa Abbe; et al. (Human Genetics, 2018)

Complete genome sequences of three novel cycloviruses identified in a dragonfly (Odonata: Anisoptera) from China - Saif Ul Islam; Wenzhong Lin; Ran Wu; Chen Lin; Waqar Islam; Muhammad Arif; Zhenguo Du; Zujian Wu (Archives of Virology, 2018)

Aflatoxin M 1 in fresh milk collected from local markets of Karachi, Pakistan - Muhammad Asif Asghar; Aftab Ahmed; Muhammad Arif Asghar (Food Additives & Contaminants Part B-Surveillance, 2018)

Petrogenesis and tectonic association of rift-related basic Panjal dykes from the northern Indian plate, North-Western Pakistan: evidence of high-Ti basalts analogous to dykes from Tibet - Muhammad Sajid; Jens Andersen; Mohammad Arif (Mineralogy and Petrology, 2018)

New natural product -an efficient antimicrobial applications of new newly synthesized pyrimidine derivatives by the electrochemical oxidation of hydroxyl phenol in the presence of 2-mercapto-6-(trifluoromethyl) pyrimidine-4-ol as nucleophile - Zia Ul Haq Khan; Amjad Khan; Pingyu Wan; Arif Ullah Khan; Kamran Tahir; Nawshad Muhammad; Faheem Ullah Khan; Hidayat Ullah Shah; Zia Ullah Khan (Natural Product Research, 2018)

Towards saving freshwater: halophytes as unconventional feedstuffs in livestock feed: a review - Mohamed E. Abd El-Hack; Dalia H. Samak; Ahmed E. Noreldin; Muhammad Arif; Hilal S. Yaqoob; Ayman A. Swelum (Environmental Science and Pollution Research, 2018)

Socio-demographic characters, distribution and transformation of iodine in soil, plant and wheat grains at District Diamer, Gilgit-Baltistan, Pakistan - Faridullah; Didar Ahmad; Hina Shabbir; Toqeer Ahmed; Muhammad Irshad; Arif Alam; Asif Sardar (Environmental Geochemistry and Health, 2018)

Complete genome sequence of a new strain of Lagenaria siceraria endornavirus from China - Xiaoqin Peng; Hui Pan; Arif Muhammad; Hongliu An; Shouguo Fang; Weimin Li; Songbai Zhang (Archives of Virology, 2018)

Remarks on genetic diversity and relationship of Punica protopunica and P. granatum assessed by molecular analyses - Muhammad Youssef; Arif Saeed Alhammadi; Jorge Humberto Ramírez-Prado; Lorenzo Felipe Sánchez-Teyer; Rosa María Escobedo-GraciaMedrano (Genetic Resources and Crop Evolution, 2018)

Evaluating the health risks of potentially toxic elements through wheat consumption in multi-industrial metropolis of Faisalabad, Pakistan - Qumber Abbas; Balal Yousaf; Guijian Liu; Muhammad Zia-ur-Rehman; Muhammad Ubaid Ali; Mehr Ahmed Mujtaba Munir; Syed Arif Hussain (Environmental Science and Pollution Research, 2017)

Assessment of heavy metals concentration in phosphate rock deposits, Hazara basin, Lesser Himalaya Pakistan - Faridullah Faridullah; Muhammad Umar; Arif Alam; Muhammad Amjad Sabir; Danyal Khan (Geosciences Journal, 2017)

Biochar soil amendment on alleviation of drought and salt stress in plants: a critical review - Shafaqat Ali; Muhammad Rizwan; Muhammad Farooq Qayyum; Yong Sik Ok; Muhammad Ibrahim; Muhammad Riaz; Muhammad Saleem Arif; Farhan Hafeez; Mohammad I. Al-Wabel; Ahmad Naeem Shahzad (Environmental Science and Pollution Research, 2017)

Single and Combined Impacts of Vitamin A and Selenium in Diet on Productive Performance, Egg Quality, and Some Blood Parameters of Laying Hens During Hot Season - Mohamed E. Abd El-Hack; Khalid Mahrose; Ali A. Askar; Mahmoud Alagawany; Muhammad Arif; Muhammad Saeed; Farzana Abbasi; Rab Nawaz Soomro; Farman Ali Siyal; Maria Tabassum Chaudhry (Biological Trace Element Research, 2017)

Alleviating the environmental heat burden on laying hens by feeding on diets enriched with certain antioxidants (vitamin E and selenium) individually or combined - Mohamed E. Abd El-Hack; Khalid Mahrose; Muhammad Arif; Maria Tabassum Chaudhry; Islam M. Saadeldin; Muhammad Saeed; Rab Nawaz Soomro; Imtiaz Hussain Raja Abbasi; Zaib Ur Rehman (Environmental Science and Pollution Research, 2017)

Maximizing maize quality, productivity and profitability through a combined use of compost and nitrogen fertilizer in a semi-arid environment in Pakistan - Shahid Iqbal; Christian Thierfelder; Haroon Zaman Khan; Hafiz Muhammad Rashad Javeed; Muhammad Arif; Muhammad Shehzad (Nutrient Cycling in Agroecosystems, 2017)

Influence of UV-A radiation on oxidative stress and antioxidant enzymes in Mythimna separata (Lepidoptera: Noctuidae) - Arif Ali; Muhammad Adnan Rashid; Qiu Ying Huang; Chao-Liang Lei (Environmental Science and Pollution Research, 2017)

Low C/N ratio raw textile wastewater reduced labile C and enhanced organic-inorganic N and enzymatic activities in a semiarid alkaline soil - Mahnaz Roohi; Muhammad Riaz; Muhammad Saleem Arif; Sher Muhammad Shahzad; Tahira Yasmeen; Muhammad Arslan Ashraf; Muhammad Atif Riaz; Ishaq A. Mian (Environmental Science and Pollution Research, 2017)

Screening of Potato Cultivars to Potato Mop-Top Virus in Northwestern Pakistan - Muhammad Arif; Ghazala Ruby; Anayatur Rehman; Murad Ali; Shamsur Rehman (Potato Research, 2016)

Individual and combined effects of crude protein, methionine, and probiotic levels on laying hen productive performance and nitrogen pollution in the manure - Mahmoud Alagawany; Mohamed E. Abd El-Hack; Muhammad Arif; Elwy A. Ashour (Environmental Science and Pollution Research, 2016)

Genetic diversity analysis of Pakistan rice (Oryza sativa) germplasm using multiplexed single nucleotide polymorphism markers - Shahid Masood Shah; Muhammad Arif; Kashif Aslam; Ghulam Shabir; Michael J. Thomson (Genetic Resources and Crop Evolution, 2016)

Comparison of antioxidant enzyme activities and DNA damage in chickpea (Cicer arietinum L.) genotypes exposed to vanadium - Muhammad Imtiaz; Muhammad Adnan Mushtaq; Muhammad Shahid Rizwan; Muhammad Saleem Arif; Balal Yousaf; Muhammad Ashraf; Xiong Shuanglian; Muhammad Rizwan; Sajid Mehmood; Shuxin Tu (Environmental Science and Pollution Research, 2016)

The potential of precision surface irrigation in the Indus Basin Irrigation System - Arif A. Anwar; Waqas Ahmad; Muhammad Tousif Bhatti; Zia Ul Haq (Irrigation Science, 2016)

Effect of UV-A radiation as an environmental stress on the development, longevity, and reproduction of the oriental armyworm, Mythimna separata (Lepidoptera: Noctuidae) - Arif Ali; Muhammad Adnan Rashid; Qiu Ying Huang; Chao-Liang Lei (Environmental Science and Pollution Research, 2016)

Contrasting effects of untreated textile wastewater onto the soil available nitrogen-phosphorus and enzymatic activities in aridisol - Muhammad Saleem Arif; Muhammad Riaz; Sher Muhammad Shahzad; Tahira Yasmeen; Alexandre Buttler; Juan Carlos Garcıa-Gil; Mahnaz Roohi; Akhtar Rasool (Environmental Monitoring and Assessment, 2016)

Copper-resistant bacteria reduces oxidative stress and uptake of copper in lentil plants: potential for bacterial bioremediation - Faisal Islam; Tahira Yasmeen; Qasim Ali; Muhammad Mubin; Shafaqat Ali; Muhammad Saleem Arif; Sabir Hussain; Muhammad Riaz; Farhat Abbas (Environmental Science and Pollution Research, 2016)

RETRACTED ARTICLE: Support vector regression methodology for prediction of output energy in rice production - Marziye Yousefi; Benyamin Khoshnevisan; Shahaboddin Shamshirband; Shervin Motamedi; Mohd Hairul Nizam Md. Nasir; Muhammad Arif; Rodina Ahmad (Stochastic Environmental Research and Risk Assessment, 2015)

Spatial distribution of pollutant emissions from crop residue burning in the Punjab and Sindh provinces of Pakistan: uncertainties and challenges - Muhammad Irfan; Muhammad Riaz; Muhammad Saleem Arif; Sher Muhammad Shahzad; Sabir Hussain; Muhammad Javed Akhtar; Leon van den Berg; Farhat Abbas (Environmental Science and Pollution Research, 2015)

Reliance of physico-mechanical properties on petrographic characteristics: consequences from the study of Utla granites, north-west Pakistan - Muhammad Sajid; Mohammad Arif (Bulletin of Engineering Geology and the Environment, 2015)

Inoculation of Nicotiana tabacum with recombinant potato virus X induces RNA interference in the solenopsis mealybug, Phenacoccus solenopsis Tinsley (Hemiptera: Pseudococcidae) - Arif Muhammad Khan; Muhammad Ashfaq; Azhar Abbas Khan; Akhtar Rasool; Javed Iqbal; Shahid Mansoor (Biotechnology Letters, 2015)

Mutation of ATF6 causes autosomal recessive achromatopsia - Muhammad Ansar; Regie Lyn P. Santos-Cortez; Muhammad Arif Nadeem Saqib; Fareeha Zulfiqar; Kwanghyuk Lee; Naeem Mahmood Ashraf; Ehsan Ullah; Xin Wang; Sundus Sajid; Falak Sher Khan; Muhammad Amin-ud-Din; Joshua D. Smith; et al. (Human Genetics, 2015)

The Early Cambrian Khewra Sandstone, Salt Range, Pakistan: endorsing southern Indian provenance - Mubashir Jehangiri; Muhammad Hanif; Muhammad Arif; Irfan U. Jan; Sajjad Ahmad (Arabian Journal of Geosciences, 2015)

Production of human interferon alpha-2b in Escherichia coli and removal of N-terminal methionine utilizing archaeal methionine aminopeptidase - Amina Arif; Qura-Tul-Ann A. Gardner; Naeem Rashid; Muhammad Akhtar (Biologia, 2015)

Petrographic and structural controls on geotechnical feasibility of dam sites: implications from investigation at Sher Dara area (Swabi), north-western Pakistan - Yasir Shaheen Khalil; Mohammad Arif; Hasnain Ali Bangash; Muhammad Sajid; Noor Muhammad (Arabian Journal of Geosciences, 2015)

Environmental quality indicators and financial development in Malaysia: unity in diversity - Arif Alam; Muhammad Azam; Alias Bin Abdullah; Ihtisham Abdul Malik; Anwar Khan; Tengku Adeline Adura Tengku Hamzah; Faridullah; Muhammad Mushtaq Khan; Hina Zahoor; Khalid Zaman (Environmental Science and Pollution Research, 2015)

Environment and air pollution: health services bequeath to grotesque menace - Muhammad Imran Qureshi; Amran Md. Rasli; Usama Awan; Jian Ma; Ghulam Ali; Faridullah; Arif Alam; Faiza Sajjad; Khalid Zaman (Environmental Science and Pollution Research, 2015)

Shigar valley gemstones, their chemical composition and origin, Skardu, Gilgit-Baltistan, Pakistan - Muhammad Hassan Agheem; Mohammad Tahir Shah; Tahseenullah Khan; Mamoru Murata; Muhammad Arif; Humaira Dars (Arabian Journal of Geosciences, 2014)

Functional analysis of the venom of mealybug parasitoid Aenasius bambawalei (Hymenoptera: Encyrtidae) - Saqi Kosar Abbas; Zain ul Abdin; Muhammad Jalal Arif; Amer Jamil (Biologia, 2014)

Petrogenesis of granites from the Utla area of Gadoon, north-west Pakistan: Implications from petrography and geochemistry - Muhammad Sajid; Mohammad Arif; M. Tahir Shah (Journal of Earth Science, 2014)

Missense mutations (p.H371Y, p.D438Y) in gene CHEK2 are associated with breast cancer risk in women of Balochistan origin - Abdul Hameed Baloch; Shakeela Daud; Nafeesa Raheem; Muhammad Luqman; Adeel Ahmad; Abdul Rehman; Jameela Shuja; Saeeda Rasheed; Akhtar Ali; Naseebullah Kakar; Hafiz Khush Naseeb; Mohammad Alam Mengal; et al. (Molecular Biology Reports, 2014)

Co-inoculation integrated with P-enriched compost improved nodulation and growth of Chickpea (Cicer arietinum L.) under irrigated and rainfed farming systems - Sher Muhammad Shahzad; Azeem Khalid; Muhammad Saleem Arif; Muhammad Riaz; Muhammad Ashraf; Zafar Iqbal; Tahira Yasmeen (Biology and Fertility of Soils, 2014)

Occurrence of potato mop-top virus in Northwest of Pakistan - Muhammad Arif; Murad Ali; Anayatur Rehman; Muhammad Fahim (European Journal of Plant Pathology, 2013)

Loasins A and B, new flavonoids from Eremostachys loasifolia - Uzma Rasheed Mughal; Ghulam Fareed; Arif Zubair; Abdul Malik; Muhammad Ali Versiani; Nighat Afza; Rasool Bakhsh Tareen (Natural Product Research, 2013)

Eggs Distribution Behaviour of Dubas Bug (Ommatissus Lybicus: Homoptera: Tropiduchidae) in Relation to Seasons and Some Physico- Morphic Characters of Date Palm Leaves - Arif Shah; Ata Ul Mohsin; Zahid Hafeez; Muhammad Naeem; Muhammad Irfan Ul Haq (Journal of Insect Behavior, 2013)

Erratum to: Three-dimensional quantitative structure–activity relationship (CoMSIA) analysis of bis-coumerine analogues as urease inhibitors - Muhammad Arif Lodhi; Zaheer-ul-Haq; Abdul Wadood; Sajid Iqbal; Khalid Mohammed Khan; Atta-ur-Rahman; Muhammad Iqbal Choudhary (Medicinal Chemistry Research, 2013)

Three-dimensional quantitative structure–activity relationship (CoMSIA) analysis of bis-coumerine analogues as urease inhibitors - Muhammad Arif Lodhi; Zaheer-ul-Haq; Abdul Wadood; Sajid Iqbal; Khalid Mohammad Khan; Atta-ur-Rahman; Muhammad Iqbal Choudhary (Medicinal Chemistry Research, 2013)

Elemental contamination in urban parks of Rawalpindi/Islamabad—a source identification and pollution level assessment study - Sajid Iqbal; Mohammad Wasim; Muhammad Tufail; Mohammad Arif; Muhammad M. Chaudhry (Environmental Monitoring and Assessment, 2012)

Optimized assay and storage conditions for enzyme activity profiling of ectomycorrhizae - Karin Pritsch; Pierre Emanuel Courty; Jean-Louis Churin; Benoit Cloutier-Hurteau; Muhammad Arif Ali; Coralie Damon; Myriam Duchemin; Simon Egli; Jana Ernst; Laurence Fraissinet-Tachet; Francisco Kuhar; Elvira Legname; et al. (Mycorrhiza, 2011)

Lung function decrement with arsenic exposure to drinking groundwater along River Indus: a comparative cross-sectional study - Asaad Ahmed Nafees; Ambreen Kazi; Zafar Fatmi; Muhammad Irfan; Arif Ali; Fujio Kayama (Environmental Geochemistry and Health, 2011)

Dynamics of resistance to organophosphate and carbamate insecticides in the cotton whitefly Bemisia tabaci (Hemiptera: Aleyrodidae) from Pakistan - Mushtaq Ahmad; M. Iqbal Arif; Muhammad Naveed (Journal of Pest Science, 2010)

In Vitro Distribution of Gold in Serum Proteins after Incubation of Sodium Aurothiomalate and Auranofin with Human Blood and its Pharmacological Significance - Mohammad S. Iqbal; Syed G. Taqi; Muhammad Arif; Muhammad Wasim; Muhammad Sher (Biological Trace Element Research, 2009)

Elaeagnoside, chymotrypsin inhibiting steroidal glucoside from Elaeagnus orientalis - Muhammad Ayaz; Muhammad Riaz; Abdul Malik; Ejaz Ahmad; Itrat Fatima; Muhammad Arif Lodhi; Muhammad Iqbal Chaudhary (Natural Product Research, 2009)

Comparative efficacy of diminazene diaceturate and diminazene aceturate for the treatment of babesiosis in horses - Hamad Bin Rashid; Mamoona Chaudhry; Haroon Rashid; Khalid Pervez; Muhammad Arif Khan; Asim Khalid Mahmood (Tropical Animal Health and Production, 2008)

‘On-farm’ seed priming with zinc in chickpea and wheat in Pakistan - David Harris; Abdul Rashid; Ghazal Miraj; Muhammad Arif; Muhammed Yunas (Plant and Soil, 2008)

Kinetics studies on triacontanyl palmitate: a urease inhibitor - Muhammad Arif Lodhi; Muhammad Athar Abbasi; Muhammad Iqbal Choudhary*; Viqar Uddin Ahmad (Natural Product Research, 2007)

Antiproliferative potential of sarcophine and its semisynthetic sulfur-containing derivatives against human mammary carcinoma cell lines - Jamal M. Arif; Swapnali S. Sawant; Khalid A. El Sayed; Muhammad Kunhi; Manogaran P. Subramanian; Yunus M. Siddiqui; Diaa T. A. Youssef; Khalid Al-Hussain; Mohammed N. Al-Ahdal; Fahad Al-Khodairy (Journal of Natural Medicines, 2007)

Chymotrypsin inhibitory constituents from Haloxylon recurvum - Ejaz Ahmed; Abdul Malik; Nighat Afza; Naheed Riaz; Itrat Anis; Ahsan Sharif; Sadia Farheen; Muhammad Arif Lodhi; Muhammad Iqbal Choudhary (Natural Product Research, 2007)

Morphological Variability of Prosopis cineraria (L.) Druce, from the Cholistan Desert, Pakistan - Mohammad Arshad; Muhammad Ashraf; Niala Arif (Genetic Resources and Crop Evolution, 2006)

Complexity analysis of stride interval time series by threshold dependent symbolic entropy - Wajid Aziz; Muhammad Arif (European Journal of Applied Physiology, 2006)

Successful computer guided planned synthesis of (4R)-thiazolidine carboxylic acid and its 2-substituted analogues as urease inhibitors - Khalid Mohammed Khan; Zia Ullah; Muhammad Arif Lodhi; Muhammad Ali; Muhammad Iqbal Choudhary; Atta ur Rahman; Zaheer ul Haq (Molecular Diversity, 2006)

Piperidines: A new class of Urease inhibitors - Khalid Mohammed Khan; Zafar S. Saify; Muhammad Arif Lodhi; Naeem Butt; Shahnaz Perveen; Ghulam Murtaza Maharvi; Muhammad Iqbal Choudhary; Atta-ur-rahman (Natural Product Research, 2006)

Structural changes in root and shoot ofBacopa monniera in response to salt stress - Gayoor Ali; A. Arif Ibrahim; Prem Shankar Srivastava; Muhammad Iqbal (Journal of Plant Biology, 1999)